Abdominal Panniculectomy Can Simplify Kidney Transplantation in Obese Patients - Promny, Dominik; Hauck, Theresa; Cai, Aijia; Arkudas, Andreas; Heller, Katharina M.; Wullich, Bernd; Apel, Hendrik; Horch, Raymund E.; Ludolph, Ingo (Urologia Internationalis, 2021)
Background: Obesity is frequently present in patients suffering from end-stage renal disease (ESRD). However, overweight kidney transplant candidates are a challenge for the transplant surgeon. Obese patients tend to develop a large abdominal panniculus after weight loss creating an area predisposed to wound-healing disorders. Due to concerns about graft survival and postoperative complications after kidney transplantation, obese patients are often refused in this selective patient cohort. The study aimed to analyze the effect of panniculectomies on postoperative complications and transplant candidacy in an interdisciplinary setting. Methods: A retrospective database review of 10 cases of abdominal panniculectomies performed in patients with ESRD prior to kidney transplantation was conducted. Results: The median body mass index was 35.2 kg/m(2) (range 28.5-53.0 kg/m(2)) at first transplant-assessment versus 31.0 kg/m(2) (range 28.0-34.4 kg/m(2)) at panniculectomy, and 31.6 kg/m(2) (range 30.3-32.4 kg/m(2)) at kidney transplantation. We observed no major postoperative complications following panniculectomy and minor wound-healing complications in 2 patients. All aside from 1 patient became active transplant candidates 6 weeks after panniculectomy. No posttransplant wound complications occurred in the transplanted patients. Conclusion: Abdominal panniculectomy is feasible in patients suffering ESRD with no major postoperative complications, thus converting previously ineligible patients into kidney transplant candidates. An interdisciplinary approach is advisable in this selective patient cohort.
CRIS-Team WoS Importer:2021-07-02

Activation of STAT3 integrates common profibrotic pathways to promote fibroblast activation and tissue fibrosis - Chakraborty, Debomita; Sumova, Barbora; Mallano, Tatjana; Chen, Chih-Wei; Distler, Alfiya; Bergmann, Christina; Ludolph, Ingo; Horch, Raymund E.; Gelse, Kolja; Ramming, Andreas; Distler, Oliver; Schett, Georg; et al. (Nature Communications, 2017)
Signal transducer and activator of transcription 3 (STAT3) is phosphorylated by various kinases, several of which have been implicated in aberrant fibroblast activation in fibrotic diseases including systemic sclerosis (SSc). Here we show that profibrotic signals converge on STAT3 and that STAT3 may be an important molecular checkpoint for tissue fibrosis. STAT3 signaling is hyperactivated in SSc in a TGF?-dependent manner. Expression profiling and functional studies in vitro and in vivo demonstrate that STAT3 activation is mediated by the combined action of JAK, SRC, c-ABL, and JNK kinases. STAT3-deficient fibroblasts are less sensitive to the pro-fibrotic effects of TGF?. Fibroblast-specific knockout of STAT3, or its pharmacological inhibition, ameliorate skin fibrosis in experimental mouse models. STAT3 thus integrates several profibrotic signals and might be a core mediator of fibrosis. Considering that several STAT3 inhibitors are currently tested in clinical trials, STAT3 might be a candidate for molecular targeted therapies of SS
EVALuna2:13455

A Myocutaneous Latissimus Dorsi Propeller Flap Based on a Single Dorsal Intercostal Perforator - Geierlehner, Alexander; Ludolph, Ingo; Arkudas, Andreas; Horch, Raymund E. (Plastic and Reconstructive Surgery Global Open, 2021)
This study presents a novel surgical technique for the reconstruction of highly challenging large lower back defects. In this case, a 72-year-old man initially diagnosed with renal cell carcinoma received nephrectomy followed by the dissection of an iliac crest metastasis and repeated high-dose irradiation therapy. Several years later, an osteocutaneous fistula at the right caudal posterior trunk made the reconstruction of the lower back defect necessary. High-dose irradiation of the lower back and poor vascular conditions at the pelvic region disqualified the patient for previously published local or free flap options. The initial strategy of an arteriovenous loop anastomosed to the femoral vessels and a free latissimus dorsi flap transfer had to be withdrawn due to repeated intraoperative loop thrombosis. For that reason, the entire latissimus dorsi muscle was used as a myocutaneous propeller flap receiving its blood supply solely through a single dorsal intercostal artery perforator. The flap survived completely and no fistulous formation occurred postoperatively. The time to complete wound healing was 4 months. This new technique is considered a valuable addition for the reconstruction of challenging posterior caudal trunk defects.
CRIS-Team WoS Importer:2021-12-03

Analysis of laboratory markers in body contouring procedures after bariatric surgery does not indicate particular risks for perioperative complications. - Stumpfe, Maximilian; Platzer, Juliane; Horch, Raymund E.; Geierlehner, Alexander; Arkudas, Andreas; Müller-Seubert, Wibke; Cai, Aijia; Promny, Theresa; Ludolph, Ingo (Perioperative Medicine, 2024)
BACKGROUND: Body contouring surgery after massive weight loss is associated with different risk factors. Wound healing disorders and seromas commonly occur postoperatively. Bariatric interventions lead to massive weight loss with excess skin and soft tissue. In this study, perioperatively collected laboratory markers of this special patient population were analyzed. METHODS: Fifty-nine patients were analyzed retrospectively regarding bariatric surgery, weight loss, body contouring surgery, laboratory markers, and complication rates. RESULTS: Body contouring surgery (n = 117) was performed in 59 patients. Weight loss was achieved after gastric bypass (40.1%), gastric banding (33.9%), or sleeve gastrectomy (26.0%), with an average of 69.2 kg. The most common body contouring procedure included abdominoplasty (n = 50), followed by thigh lift (n = 29), mammaplasty (n = 19), brachioplasty (n = 14), and upper body lift (n = 5). Analysis of laboratory markers revealed no exceptional and clinically relevant variations. Correlation analysis revealed associations between resection weight, amount of drain fluid, and particular laboratory markers. CONCLUSION: Analysis of perioperative laboratory markers in this special patient population after massive weight loss did not indicate clinically relevant risk factors regardless of the type of bariatric or body contouring surgery. Body contouring surgeries after bariatric interventions prove to be safe and low risk concerning perioperative laboratory markers and postoperative hospitalization.
EVALuna2:574369

A Personalized Approach to Treat Advanced Stage Severely Contracted Joints in Dupuytren’s Disease with a Unique Skeletal Distraction Device—Utilizing Modern Imaging Tools to Enhance Safety for the Patient - Müller-Seubert, Wibke; Cai, Aijia; Arkudas, Andreas; Ludolph, Ingo; Fritz, Niklas; Horch, Raymund E. (Journal of Personalized Medicine, 2022)
Background: While surgical therapy for Dupuytren’s disease is a well-established standard procedure, severe joint flexion deformities in advanced Dupuytren’s disease remain challenging to treat. Skeletal distraction has proven to be an additional treatment option. Methods: We analyzed the surgical treatment algorithm, including the application of a skeletal distraction device, in patients with a flexion deformity due to Dupuytren’s disease, Iselin stage III or IV, who were operated on from 2003 to 2020 in our department. Results: From a total of 724 patients, we included the outcome of 55 patients’ fingers in this study, who had undergone additional skeletal joint distraction with our Erlangen device. Additional fasciotomy or fasciectomy, in a one-or two-staged procedure, was performed in all patients, according to the individual findings and necessities. The range of motion of the PIP joint improved from 12◦ to 53◦. A number of complications, in all steps of the treatment, were noted in a total of 36.4% of patients, including the development of fractures (16.4%), followed by vessel injury, pin infections, and complex regional pain syndrome (5%). Conclusions: Additional skeletal distraction improves the range of motion of severely contracted joints in Dupuytren’s disease. Nevertheless, careful patient selection is necessary, due to the moderate rate of complications.
CRIS-Team Scopus Importer:2022-03-25
Keywords: Distracted driving; Dupuytren contracture; Joint dislocation

Aspergillus fumigatus Spores Are Not Able to Penetrate Silicone Breast Implant Shells - Horch, Raymund E.; Krappmann, Sven; Duemig, Michaela; Schmitz, Marweh; Kengelbach-Weigand, Annika; Schubert, Dirk W.; Kremser, Thomas; Bogdan, Christian; Ludolph, Ingo (Annals of Plastic Surgery, 2019)
Bacterial contamination is hypothesized to be one reason for the development of capsular contracture after alloplastic breast reconstruction using silicone breast implants. The role of fungal colonization or infection in this context as well as the question if microorganisms can penetrate the shell of silicone breast implants remains an unresolved question to date. Therefore, the aim of this study was to assess whether fungal spores are able to penetrate the shell of silicone implants. In an experimental in vitro setup with different arrangements of growth compartments, silicone chambers were placed in culture dishes filled with Aspergillus minimal medium or liquid culture medium. Inoculation was performed with conidia of Aspergillus fumigatus and incubated for seven days. On a daily basis, plates were inspected for conidial germination and hyphal growth. In none of the different experimental settings nutrients or hyphae of Aspergillus fumigatus were able to penetrate the silicone material.ConclusionsFungal spores and hyphae do not permeate through an intact silicone shell used in breast implants; thus, the silicone material serves as an impenetrable barrie
Keywords: Aspergillus fumigatus; penetration; silicone implants; breast

Bildgebende Diagnostik zur Therapieplanung bei Lip- und Lymphödem - Zetzmann, Katharina; Ludolph, Ingo; Horch, Raymund E.; Boos, Anja (Phlebologie, 2020)
Lipoedema is a progressive disease, which predominantly affects women. It is characterised by circumferential growth, with increase in fat tissue of the extremities, and can lead to oedema. In contrast, the lymphoedema is defined by a specific lymphatic drainage disorder and can lead to fibrosis of the surrounding connective tissue. While lipoedema is diagnosed through clinical symptoms and diagnostic imaging can usually only be used to rule out comorbidities, lymphatic drainage disorder can be visualised using imaging methods. Ultrasound is a basis diagnostic tool to show retained interstitial fluid in lip-and lymphoedema. Lymphoscintigraphy is considered to be the gold standard to demonstrate a lymphatic drainage disorder, which can be combined with computed tomography. Indocyanine green(ICG) lymphography is a dynamic imaging tool, which is of increasing significance due to its possible intraoperative use. Magnetic resonance imaging (MRI) lymphography has the ability to visualise a lymphoedema and a lymphatic drainage disorder in three dimensions and is therefore considered to be a meaningful supplement. Therapy of lip-and lymphoedema should always be based on a combination of conservative and surgical strategies. While liposuction and other resection procedures can lead to symptom relief in lipedoema or advanced lymphoedema, newer reconstructive pro cedures such as lymph node transplantation or lymphovenous anastomoses are modern techniques to treat lymphoedema. A long lasting volume reduction can be achieved by creating new lymphatic pathways leading to improved quality of life and reduced symptoms.
CRIS-Team Scopus Importer:2020-05-02
Keywords: liposuction

Body Contouring Surgery Improves Physical Activity in Patients After Massive Weight Loss—a Retrospective Study - Maringa, Linda; Hauck, Theresa; Boos, Anja; Schmitz, Marweh; Arkudas, Andreas; Horch, Raymund E.; Ludolph, Ingo; Cai, Aijia (Obesity Surgery, 2019)
Background: The aim of the study was to compare physical activity (PA) in patients who had undergone massive weight loss (MWL), before and after body contouring procedures. Methods: All patients undergoing body contouring surgery after MWL between 2007 and 2017 with a minimum follow-up of 6 months after the last procedure were included in this retrospective study. Excluded were those with a body mass index > 35 kg/m2 and those with comorbidities leading to impaired PA. Quality of life (QOL) was assessed using the Moorehead-Ardelt QOL Questionnaire II. Evaluation of PA was obtained with the International Physical Activity Questionnaire (IPAQ) short form and the Freiburg PA Questionnaire. Functional impairment during exercise was analyzed using a self-designed functional impairment score (FIS). Results: In the 45 patients completing the survey (37 female, 8 male), an improvement in QOL (p < 0.001) and PA scored by the IPAQ (p = 0.017) was found. The Freiburg PA Questionnaire showed no difference in PA before and after body contouring surgery (p = 0,274). Furthermore, scores of the FIS indicated a decrease of functional impairment during physical activity after body contouring surgery (p < 0.001). Conclusion: Body contouring improves QOL and PA in patients after massive weight loss. The results of our study confirm the important role of plastic surgery in the treatment and maintenance of health of patients with former obesity.
CRIS-Team Scopus Importer:2019-09-03
Keywords: Body contouring surgery; Massive weight loss; Physical activity; Quality of life

Calcium, magnesium and aluminium ions as decontaminating agents against dermal fluoride absorption following hydrofluoric acid exposure - Mini Vijayan, Suvarna; Göen, Thomas; Dennerlein, Kathrin; Horch, Raymund E.; Ludolph, Ingo; Drexler, Hans; Kilo, Sonja (Toxicology in Vitro, 2021)
The fluoride ions of the industrially largely irreplaceable, locally corrosive hydrofluoric acid (HF) can scavenge cations in biological tissues, which explains their high toxic potential, and also leads to local acidification through proton release. The influence of three complexing agents, calcium (Ca2+) gluconate (as 2.5% Ca2+gel and individually (2.84%) or commercially (10%) formulated Ca2+solution), magnesium (Mg2+) gluconate (2.84%) solution and aluminium (Al3+) solution (Hexafluorine®, pure and diluted) on the absorption of fluoride following HF exposure (1–3 min, 100 μl, 30%/0.64 cm2) through human skin was investigated in an ex-vivo diffusion cell model. Fluoride absorption was assessed over 6–24 h and analysed with a fluoride electrode. Decreasing the contamination time reduced the fluoride absorption distinctly which was further reduced by the application of fluoride-binding decontamination agents (Ca2+, Mg2+, Al3+) or water alone without being significantly different. Ca2+ appeared slightly more effective than Mg2+ in reducing fluoride absorption. Moreover, the addition of pH adjusting buffer promoted the decontamination efficacy. Fluoride-binding agents can facilitate the decontamination of dermal HF exposure. However, prompt decontamination appeared to be the key to successful limitation of fluoride absorption and pushes the choice of decontamination agent almost into the background.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Aluminium; Calcium gluconate; Decontamination; Fluoride absorption; Human skin; Hydrofluoric acid

Changes of perfusion patterns of surgical wounds under application of closed incision negative pressure wound therapy in postbariatric patients - Renno, Isabell; Boos, Anja; Horch, Raymund E.; Ludolph, Ingo (Clinical Hemorheology and Microcirculation, 2019)
BACKGROUND: Negative pressure wound therapy applied over closed incisions (ciNPT) has been shown to influence wound healing. Therefore, the aim of this study was to examine the short-term effects of ciNPT on skin perfusion patterns in postbariatric wounds.
CRIS-Team WoS Importer:2019-08-20

Commentary on JPRAS-D-18-00185: The use of Laser Speckle Contrast Imaging to predict flap necrosis: An experimental study in a porcine flap model article - Ludolph, Ingo; Horch, Raymund E. (Journal of Plastic Reconstructive and Aesthetic Surgery, 2019)
CRIS-Team WoS Importer:2019-05-07

Comment on: One-stage wound healing of fingertip injury induced by treatment of artificial dermis - Ludolph, Ingo; Horch, Raymund E. (Handchirurgie, Mikrochirurgie, Plastische Chirurgie, 2018)
The presented study provides an overview about fingertip injuries and the use of artificial dermis for wound coverage. In specialized centers fingertip injuries are extremely common, independent of the patient ' s age and sex. In the real world probably a considerable number of unreported cases are not referred to a hand surgeon, because such injuries are often misjudged as a minor trauma. Due to this fact, an easy to learn and widely available surgical treatment would be useful. As a result of inadequate treatment beside cosmetic aspects true functional sequelae may occur negatively influencing patients quality of life up to temporary disability or even invalidity. We appreciate the authors conclusion that the complete treatment should be performed by a specialist whenever possible.
EVALuna2:211475

Complications and their management following axillary, inguinal and iliac lymph node dissection - Ludolph, Ingo; Arkudas, Andreas; Müller-Seubert, Wibke; Cai, Aijia; Horch, Raymund E. (Die Chirurgie, 2022)
Irrespective of numerous technical developments, lymphadenectomy remains a necessary component of surgical tumor therapy. Depending on the extent and anatomical localization, complications associated with the lymph vessels such as lymphoceles, lymphatic fistulas or secondary lymphedema can occur with varying frequency, despite a meticulous dissection technique. Chronic lymph fistulas or lymphoceles often require interventional or surgical procedures. Pedicled or free microsurgical flaps are often required in the case of coexisting wound healing disorders or skin soft tissue defects, especially in an irradiated area. For secondary lymphedema a number of conservative and surgical treatment methods have been established. Adequate guideline-based conservative treatment is the method of first choice. If this does not lead to the desired result, microsurgical reconstructive, deviating or resecting procedures are available.
CRIS-Team WoS Importer:2022-11-04

Corrigendum: Does indocyanine green fluorescence angiography impact the intraoperative choice of procedure in free vascularized medial femoral condyle grafting for scaphoid non-unions?(Front. Surg., (2022), 9, (962450), 10.3389/fsurg.2022.962450) - Mulica, Markus; Horch, Raymund E.; Arkudas, Andreas; Cai, Aijia; Müller-Seubert, Wibke; Hauck, Theresa; Ludolph, Ingo (Frontiers in Surgery, 2023)
Incorrect Author Name In the published article, the authors namewere written asMulicaMarkus, Horch Raymund, Arkudas Andreas, Cai Aijia, Müller-SeubertWibke, Hauck Theresa and Ludolph Ingo The correct name order is (first name and surname). Markus Mulica, Raymund E. Horch, Andreas Arkudas, Aijia Cai, Wibke Müller- Seubert, Theresa Hauck, Ingo Ludolph Error in Figure Legend In the published article, there was an error in the legend for Figure 5 as published.
CRIS-Team Scopus Importer:2023-02-24
Keywords: free vascularized bone graft; indocyanine green angiography; medial femoral condyle bone graft; scaphoid non-union; union rate

Cracking the perfusion code?: Laser-assisted Indocyanine Green angiography and combined laser Doppler spectrophotometry for intraoperative evaluation of tissue perfusion in autologous breast reconstruction with DIEP or ms-TRAM flaps - Ludolph, Ingo; Arkudas, Andreas; Schmitz, Marweh; Boos, Anja; Taeger, Christian; Rother, Ulrich; Horch, Raymund E.; Beier, Justus (Journal of Plastic Reconstructive and Aesthetic Surgery, 2016)
The aim of this prospective study was to assess the correlation of flap perfusion analysis based on laser-assisted Indocyanine Green (ICG) angiography with combined laser Doppler spectrophotometry in autologous breast reconstruction using free DIEP/ms-TRAM flaps. Between February 2014 and July 2015, 35 free DIEP/ms-TRAM flaps were included in this study. Besides the clinical evaluation of flaps, intraoperative perfusion dynamics were assessed by means of laser-assisted ICG angiography and post-capillary oxygen saturation and relative haemoglobin content (rHb) using combined laser Doppler spectrophotometry. Correlation of the aforementioned parameters was analysed, as well as the impact on flap design and postoperative complications. Flap survival rate was 100%. There were no partial flap losses. In three cases, flap design was based on the angiography, contrary to clinical evaluation and spectrophotometry. The final decision on the inclusion of flap areas was based on the angiographic perfusion pattern. Angiography and spectrophotometry showed a correlation in most of the cases regarding tissue perfusion, post-capillary oxygen saturation and relative haemoglobin content. Laser-assisted ICG angiography is a useful tool for intraoperative evaluation of flap perfusion in autologous breast reconstruction with DIEP/ms-TRAM flaps, especially in decision making in cases where flap perfusion is not clearly assessable by clinical signs and exact determination of well-perfused flap margins is difficult to obtain. It provides an objective real-time analysis of flap perfusion, with high sensitivity for the detection of poorly perfused flap areas. Concerning the topographical mapping of well-perfused flap areas, laser-assisted angiography is superior to combined laser Doppler spectrophotometry.
EVALuna2:15280

Dipeptidylpeptidase 4 as a Marker of Activated Fibroblasts and a Potential Target for the Treatment of Fibrosis in Systemic Sclerosis - Soare, Alina; Györfi, Andrea-Hermina; Matei, Alexandru-Emil; Dees, Clara; Rauber, Simon; Wohlfahrt, Thomas; Chen, Chih Wei; Ludolph, Ingo; Horch, Raymund E.; Bäuerle, Tobias; von Hörsten, Stephan; Mihai, Carina; et al. (Arthritis and Rheumatology, 2020)
Objective: Expression of dipeptidylpeptidase 4 (DPP-4) identifies a dermal fibroblast lineage involved in scarring during wound healing. The role of DDP-4 in tissue fibrosis is, however, unknown. The aim of the present study was to evaluate DPP-4 as a potential target for the treatment of fibrosis in patients with systemic sclerosis (SSc). Methods: Expression of DPP-4 in skin biopsy samples and dermal fibroblasts was analyzed by real-time polymerase chain reaction, immunofluorescence, and Western blot analyses. The activity of DPP-4 was modulated by overexpression, knockdown, and pharmacologic inhibition of DPP4 using sitagliptin and vildagliptin. The effects of DPP4 inhibition were analyzed in human dermal fibroblasts and in different mouse models of SSc (each n = 6). Results: The expression of DPP-4 and the number of DPP-4–positive fibroblasts were increased in the fibrotic skin of SSc patients, in a transforming growth factor β (TGFβ)–dependent manner. DPP-4–positive fibroblasts expressed higher levels of myofibroblast markers and collagen (each P < 0.001 versus healthy controls). Overexpression of DPP4 promoted fibroblast activation, whereas pharmacologic inhibition or genetic inactivation of DPP4 reduced the proliferation, migration, and expression of contractile proteins and release of collagen (each P < 0.001 versus control mice) by interfering with TGFβ-induced ERK signaling. DPP4-knockout mice were less sensitive to bleomycin-induced dermal and pulmonary fibrosis (P < 0.0001 versus wild-type controls). Treatment with DPP4 inhibitors promoted regression of fibrosis in mice that had received bleomycin challenge and mice with chronic graft-versus-host disease, and ameliorated fibrosis in TSK1 mice (each P < 0.001 versus untreated controls). These antifibrotic effects were associated with a reduction in inflammation. Conclusion: DPP-4 characterizes a population of activated fibroblasts and shows that DPP-4 regulates TGFβ-induced fibroblast activation in the fibrotic skin of SSc patients. Inhibition of DPP4 exerts potent antifibrotic effects when administered in well-tolerated doses. As DPP4 inhibitors are already in clinical use for diabetes, these results may have direct translational implications for the treatment of fibrosis in patients with SSc.
CRIS-Team Scopus Importer:2020-01-10

Effects of Different Pressure Levels in Topical Negative Pressure Application-Analysis of Perfusion Parameters in a Clinical Skin Model Using Multimodal Imaging Techniques - Aslan-Horch, Emine Ceylan; Horch, Raymund E.; Arkudas, Andreas; Müller-Seubert, Wibke; Ludolph, Ingo (Journal of Clinical Medicine, 2022)
The effects of topical negative pressure therapy (TNP) have been a subject of research for many years. In this study, we investigated new imaging devices to detect clinical changes that TNP causes on healthy tissue and identified differences in microcirculation created by different pressure levels. We used near-infrared spectroscopy (NIS), thermography, and a vein illuminator to measure the differences in oxygen saturation, tissue temperature, and vein pattern. A control group (-125 mmHg) and three comparison groups with only TNP dressing (Group 1), -25 mmHg (Group 2), and -175 mmHg (Group 3) were established. Thirty minutes of TNP on intact skin was followed by 30 min of resting. A total of 24 participants were measured by all imaging devices at predetermined time points. Oxygen saturation and skin temperature increased by 8.07% and 1.67 degrees C for the control group, 4.00% and 1.65 degrees C for Group 2, and 8.45% and 1.68 degrees C for Group 3. Group 1 showed a slight increase in oxygen saturation and a 2.7 degrees C increase in skin temperature. Over the 30 min following removal of TNP, oxygen saturation and temperature decreased gradually for all groups. The vein illuminator did not show significant differences in the venous pattern or flow. Our study showed that higher negative pressure values resulted in higher oxygen saturation and higher tissue temperature.
CRIS-Team WoS Importer:2022-09-16

ENGRAILED 1 COORDINATES CYTOSKELETAL ORGANIZATION TO PROMOTE MYOFIBROBLAST DIFFERENTIATION AND FIBROTIC TISSUE REMODELING - Györfi, Andrea-Hermina; Matei, Alexandru-Emil; Fuchs, Maximilian; Rigau, Aleix; Hong, Xuezhi; Honglin, Z.; Luber, M.; Bergmann, Christina; Dees, Clara; Ludolph, Ingo; Horch, Raymund E.; Distler, O.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2021)
CRIS-Team WoS Importer:2021-10-01

Engrailed 1 coordinates cytoskeletal reorganization to induce myofibroblast differentiation - Györfi, Andrea-Hermina; Matei, Alexandru-Emil; Fuchs, Maximilian; Liang, Chunguang; Rigau, Aleix; Hong, Xuezhi; Zhu, Honglin; Luber, Markus; Bergmann, Christina; Dees, Clara; Ludolph, Ingo; Horch, Raymund E.; et al. (Journal of Experimental Medicine, 2021)
Transforming growth factor-β (TGFβ) is a key mediator of fibroblast activation in fibrotic diseases, including systemic sclerosis. Here we show that Engrailed 1 (EN1) is reexpressed in multiple fibroblast subpopulations in the skin of SSc patients. We characterize EN1 as a molecular amplifier of TGFβ signaling in myofibroblast differentiation: TGFβ induces EN1 expression in a SMAD3-dependent manner, and in turn, EN1 mediates the profibrotic effects of TGFβ. RNA sequencing demonstrates that EN1 induces a profibrotic gene expression profile functionally related to cytoskeleton organization and ROCK activation. EN1 regulates gene expression by modulating the activity of SP1 and other SP transcription factors, as confirmed by ChIP-seq experiments for EN1 and SP1. Functional experiments confirm the coordinating role of EN1 on ROCK activity and the reorganization of cytoskeleton during myofibroblast differentiation, in both standard fibroblast culture systems and in vitro skin models. Consistently, mice with fibroblast-specific knockout of En1 demonstrate impaired fibroblast-to-myofibroblast transition and are partially protected from experimental skin fibrosis.
CRIS-Team Scopus Importer:2021-07-30

Enhancing Safety in Reconstructive Microsurgery Using Intraoperative Indocyanine Green Angiography - Ludolph, Ingo; Horch, Raymund E.; Arkudas, Andreas; Schmitz, Marweh (Frontiers in Surgery, 2019)
Intraoperative assessing and postoperative monitoring of the viability of free flaps is of high relevance in reconstructive microsurgery. Today different methods for the evaluation of tissue perfusion are known. Indocyanine Green angiography is an emerging technique among plastic surgeons with a broad scope of applications especially in microsurgical free flap transfer. We demonstrate the value and clinical application of this technique based on representative selected cases where Indocyanine Green angiography was used in microsurgical free flap transfers from different anatomic donor sites during the operation. Hereby perforator selection, flap tailoring, changes of blood flow and patency of anastomoses was judged and decision making was based on the angiographic findings. This method has proven to be valid, reproducible and easy to use. The application is not limited to the evaluation of skin perfusion, but is also applicable to muscle tissue or chimeric or composite flaps. Reliable judgement is especially given for the extent of arterially perfused tissue following complete flap dissection. Moreover, this real-time angiography revealed a high sensitivity for the detection of poorly perfused flap areas, thus supporting the conventional clinical judgement and reducing complications. In summary Indocyanine Green angiography has the potential to reduce flap related complications and to contribute to enhancing and extending the possibilities of free flap surgery.
CRIS-Team WoS Importer:2019-07-16

Evaluation of the Influence of Short Tourniquet Ischemia on Tissue Oxygen Saturation and Skin Temperature Using Two Portable Imaging Modalities - Müller-Seubert, Wibke; Herold, Helen; Graf, Stephanie; Ludolph, Ingo; Horch, Raymund E. (Journal of Clinical Medicine, 2022)
Background: The exact influence of tourniquet ischemia on a treated extremity remains unclear. Methods: Twenty patients received an operation on one hand under tourniquet ischemia. Twenty healthy volunteers received 10 min of tourniquet ischemia on one of their arms. Measurements of tissue oxygen saturation using near-infrared reflectance-based imaging and skin temperature of the dorsum of the hand were performed at five different timepoints (t0 was performed just before the application of the tourniquet ischemia, t1 directly after the application of the tourniquet ischemia, t2 before the release of the ischemia, t3 directly after the release of the ischemia, and t4 on the following day). Results: In both groups, tissue oxygen saturation dropped after the application of the tourniquet ischemia compared to t0 and increased after the release of the tourniquet ischemia. In the patient group, tissue oxygen saturation at t4 was higher compared to t0; in contrast, the level of tissue oxygen saturation in the participant group dropped slightly at t4 compared to t0. The measured skin temperature in the patient group showed an increase during the observation period, while it continuously decreased in the group of healthy participants. Conclusions: Short-term ischemia did not appear to permanently restrict perfusion in this study design. The non-invasive imaging modalities used were easy to handle and allowed repetitive measurement.
CRIS-Team WoS Importer:2022-09-16

External screw-threaded traction device helps optimize finger joint mobility in severe stage III and IV dupuytren disease - Horch, Raymund E.; Schmitz, Marweh; Kreuzer, Maria; Arkudas, Andreas; Ludolph, Ingo; Müller-Seubert, Wibke (Medical Science Monitor, 2021)
Background: Treating advanced finger joint contractures from Dupuytren disease remains a challenge. We evaluated the effectiveness of a skeletal distraction device versus alternative treatment options. Material/Methods: We analyzed the surgical treatment of contracted finger joints in stage III and stage IV Dupuytren’s disease over a 10-year period. Data were obtained from inpatient and outpatient medical records, including postoperative clinical examinations and extended Disabilities of the Arm, Shoulder, and Hand (DASH) questionnaire scores. Complications of infection, postoperative pain, and wound healing disorders were recorded. Results: A total of 79 patients (83 hands) were assigned to 2 treatment groups. Patients in group 1 underwent an initial open transection of the main fibrous cord, Z-plasty, distraction with the Erlangen external distraction device, and fasciectomy. The distraction period was 13 to 81 days (mean 31 days). Group 2 underwent a conventional single-stage fasciectomy and arthrolysis. DASH scores and subjective patient satisfaction were lower in group 1 (20.7/33%) than in group 2 (10.3/50%). However, the staged approach of group 1 to treat proximal interphalangeal joint contractures in the long term (improvement >40%) was more effective than the approach of group 2 (>33%). Distraction device pin infections occurred in 20% of hands. Postoperative pain and complex regional pain syndrome type I occurred in 25% of hands in group 1 and 3% in group 2. Conclusions: A screw thread driven external fixation device is useful in end-stage Dupuytren’s finger joint contractures. It is indicated when joint contractures are advanced and simple arthrolysis is insufficient.
CRIS-Team Scopus Importer:2021-03-26
Keywords: Dupuytren contracture; External fixators; Joint capsule release

Imaging Diagnostics for Therapy Planning for Lipodema and Lymphodema Reply - Boos, Anja M.; Ludolph, Ingo; Horch, Raymund E. (Phlebologie, 2020)
CRIS-Team WoS Importer:2020-12-18

Imaging for treatment planning in lipo-and lymphedema - Zetzmann, Katharina; Ludolph, Ingo; Horch, Raymund E.; Boos, Anja (Handchirurgie, Mikrochirurgie, Plastische Chirurgie, 2018)
Lipoedema is a progressive disease, which predominantly affects women. It is characterised by circumferential growth, with increase in fat tissue of the extremities, and can lead to oedema. In contrast, the lymphoedema is defined by a specific lymphatic drainage disorder and can lead to fibrosis of the surrounding connective tissue. While lipoedema is diagnosed through clinical symptoms and diagnostic imaging can usually only be used to rule out comorbidities, lymphatic drainage disorder can be visualised using imaging methods. Ultrasound is a basis diagnostic tool to show retained interstitial fluid in lip- and lymphoedema. Lymphoscintigraphy is considered to be the gold standard to demonstrate a lymphatic drainage disorder, which can be combined with computed tomography. Indocyanine green(ICG) lymphography is a dynamic imaging tool, which is of increasing significance due to its possible intraoperative use. Magnetic resonance imaging (MRI) lymphography has the ability to visualise a lymphoedema and a lymphatic drainage disorder in three dimensions and is therefore considered to be a meaningful supplement. Therapy of lip- and lymphoedema should always be based on a combination of conservative and surgical strategies. While liposuction and other resection procedures can lead to symptom relief in lipedoema or advanced lymphoedema, newer reconstructive procedures such as lymph node transplantation or lymphovenous anastomoses are modern techniques to treat lymphoedema. A long lasting volume reduction can be achieved by creating new lymphatic pathways leading to improved quality of life and reduced symptoms.
EVALuna2:211463

Impact of physiologically relevant temperatures on dermal absorption of active substances - an ex-vivo study in human skin - Kilo, Sonja; Wick, J.; Mini Vijayan, Suvarna; Göen, Thomas; Horch, Raymund E.; Ludolph, Ingo; Drexler, Hans (Toxicology in Vitro, 2020)
Skin temperature plays a certain role in the dermal absorption of substances, but the extent and mechanisms of skin temperatures-induced modulation in ranges caused by physiological thermoregulation or environmental conditions are largely unknown. The influence of dermal temperature on the absorption of the model lipophilic compound (anisole) and the model hydrophilic compounds (1,4-dioxane, ethanol) through human skin was investigated at three dermal temperatures (25, 32 and 39 °C) in an ex-vivo diffusion cell model. The substances were applied to the skin and transdermal penetration was monitored. All substances showed temperature dependent variations in their penetration behavior (3 h: 25–39 °C: 202–275% increase in cumulative, transdermally penetrated amounts). The relative differences in absorption in relation to temperature were greatest within 45 min after exposure (25–39 °C: 347–653% rise in cumulated penetration), although absolute amounts absorbed were small (45 min vs. 3 h: 4.5–14.5%). Regardless of blood circulation, skin temperature significantly influences the amount and kinetics of dermal absorption. Substance-dependent, temperature-related changes of the lipid layer order or the porous pathway may facilitate penetration. The early-stage modulation of transdermal penetration indicates transappendageal absorption, which may be relevant for short-term exposures. For both, toxicological evaluation and perfusion cell studies, it is important to consider the thermal influence on absorption or to perform the latter at a standardized temperature (32±1 °C).
CRIS-Team Scopus Importer:2020-09-11
Keywords: Dermal absorption; Diffusion cell; Influence of temperature; Transdermal penetration

Impact of skin temperature and intradermal pH on transdermal fluoride absorption following hydrofluoric acid exposure: An ex vivo diffusion cell study in human skin - Mini Vijayan, Suvarna; Wolfschmidt, Anna; Göen, Thomas; Horch, Raymund E.; Ludolph, Ingo; Drexler, Hans; Kilo, Sonja (Toxicology Letters, 2025)
Accidents involving hydrofluoric acid (HF) can cause systemic poisoning due to the transdermal absorption of fluoride ions. The present study investigates the impact of skin temperature and intradermal pH on fluoride absorption and its kinetics. Human skin was exposed to 30 % HF for 3 minutes using a static diffusion cell model. The study compared cumulative fluoride absorption at two different skin temperatures (24°C and 32°C) and two intradermal pH values (6.5 and 7.2). Experiments were performed at least three times per treatment and per donor (n = 5), over a duration of 8 h and 12 h for pH and temperature experiments, respectively. Results showed that fluoride absorption increased with temperature, with a ∼17.8 % increase in cumulative penetration at 32°C compared to 24°C. The maximum flux rate through the skin was reached within the first hour and was ∼54 % lower at 24°C. Additionally, acidifying the skin to an intradermal pH of 6.5 led to a significant increase in cumulative fluoride absorption by ∼12.6 % and a ∼50.3 % increase in the maximum flux rate. The findings suggest that reducing fluoride absorption after accidental skin contact with HF may be achieved by lowering skin temperature and buffering intradermal pH to a physiological level. These results have important implications for first-aid measures in real-life scenarios involving HF exposure. Controlling skin temperature by cooling and intradermal pH with the addition of buffering agents may enhance decontamination strategies.
CRIS-Team Scopus Importer:2025-05-23
Keywords: Clinical significance; Ex Vivo human skin; Franz Diffusion cell; Hydrofluoric acid; Intradermal pH; Skin temperature; Transdermal fluoride absorption

Improving the Safety of DIEP Flap Transplantation: Detailed Perforator Anatomy Study Using Preoperative CTA† - Frank, Katharina; Stroebel, Armin; Ludolph, Ingo; Hauck, Theresa; May, Matthias; Beier, Justus; Horch, Raymund E.; Arkudas, Andreas (Journal of Personalized Medicine, 2022)
Background: Deep inferior epigastric perforator and muscle sparing transverse rectus abdominis muscle flaps are commonly used flaps for autologous breast reconstruction. CT-angiography allows to analyse the perforator course preoperatively. Our aim was to compare the different aspects of perforator anatomy in the most detailed study. Methods: CT-angiographies of 300 female patients with autologous breast reconstruction of 10 years were analysed regarding the anatomy of the deep inferior epigastric artery and every perforator. Results: Overall, 2260 perforators were included. We identified correlations regarding the DIEA branching point and number of perforators and their intramuscular course. The largest perforator emerged more often from the medial branch of the DIEA than the smaller perforators (70% (416/595) vs. 54% (878/1634), p < 0.001) and more often had a direct connection to the SIEV (large 67% (401/595) vs. small 39% (634/1634), p < 0.01). Medial row perforators were larger than the laterals (lateral 1.44 mm ± 0.43 (n = 941) vs. medial 1.58 mm ± 0.52 (n = 1304) (p < 0.001)). The larger and more medial the perforator, the more likely it was connected to the SIEV: perforators with direct connection to the SIEV had a diameter of 1.65 mm ± 0.53 (n = 1050), perforators with indirect connection had a diameter of 1.43 ± 0.43 (n = 1028), perforators without connection had a diameter of 1.31 mm ± 0.37 (n = 169) (p < 0.001). Medial perforators were more often directly connected to the SIEV than lateral perforators (medial 56% (723/1302) vs. lateral 35% (327/941), p < 0.001). A lateral perforator more often had a short intramuscular course than medial perforators (69% (554/800) vs. 45% (474/1055), p < 0.001), which was also more often observed in the case of a small perforator and a caudal exit of the rectus sheath. Conclusion: The largest perforator emerges more often from the medial branch of the DIEA and frequently has a direct connection to the SIEV, making medial row perforators ideal for DIEP flap transplantation.
CRIS-Team Scopus Importer:2022-06-10
Keywords: autologous breast reconstruction; CTA; DIEP flap; MS-TRAM flap; perforator

Indocyanine green angiography and the old question of vascular autonomy - Long term changes of microcirculation in microsurgically transplanted free flaps - Ludolph, Ingo; Arkudas, Andreas; Lang, Werner; Rother, Ulrich; Horch, Raymund E.; Cai, Aijia (Clinical Hemorheology and Microcirculation, 2019)
BACKGROUND: Free tissue transfer has become a routine procedure with low failure. In case of a compromised vascular pedicle, flap survival is time dependantly possible due to flap autonomization. However it remains unknown at what time and to which degree different factors influence flap autonomization.
CRIS-Team WoS Importer:2019-10-15

Interdisciplinary Surgical Approaches in Vaginal and Perineal Reconstruction of Advanced Rectal and Anal Female Cancer Patients - Horch, Raymund E.; Ludolph, Ingo; Weber, Klaus; Grützmann, Robert; Arkudas, Andreas; Cai, Aijia (Frontiers in Oncology, 2020)
Relapsing or far advanced rectal and anal cancers remain difficult to treat and require interdisciplinary approaches. Due to modern standard protocols all patients receive irradiation and neoadjuvant chemotherapy—and in case of a relapse a second irradiation—rendering the surgical site prone to surgical site infections and oftentimes long lasting sinus and septic complications after exenteration in the pelvis. Despite an improved overall survival rate in these patients the downside of radical tumor surgery in the pelvis is a major loss of quality of life, especially in women when parts of the vagina need to be resected. Derived from our experince with over 300 patients receiving pelvic and perineal reconstruciton with a transpelvic vertical rectus abdominis myocutaneous (tpVRAM) flap we studied the impact of this surgical technique on the outcomes of female patients with or without vaginal reconstruction following pelvic exenteration. We found out that the tpVRAM flap is reliably perfused and helps to reduce long term wound healing desasters in the irradiated perineal/vaginal/gluteal region.
CRIS-Team Scopus Importer:2020-06-02
Keywords: anal cancer; rectal cancer; transpelvic vertical rectus abdominis myocutaneous flap; vaginal reconstruction; VRAM

Interdisciplinary Surgical Therapy of Extremity Soft-Tissue Sarcomas: A Personalized Resection and Reconstruction Algorithm - Osterloh, Justus; Ludolph, Ingo; Grützmann, Robert; Meyer, Alexander; Lang, Werner; Horch, Raymund E.; Fechner, Katja; Arkudas, Andreas (Journal of Personalized Medicine, 2023)
Soft-tissue sarcomas (STS) are rare, but potentially life-threatening malignancies. STS can occur anywhere in the human body with the limbs being the most common site. Referral to a specialized sarcoma center is crucial to guarantee prompt and appropriate treatment. STS treatment strategies should be discussed in an interdisciplinary tumor board to involve expertise from all available resources, including an experienced reconstructive surgeon for an optimal outcome. In many cases, extensive resection is needed to achieve R0 resection, resulting in large defects after surgery. Hence, an evaluation of whether plastic reconstruction might be required is mandatory to avoid complications due to insufficient primary wound closure. In this retrospective observational study, we present data of patients with extremity STS treated at the Sarcoma Center, University Hospital Erlangen, in 2021. We found that complications were more frequent in patients who received secondary flap reconstruction after insufficient primary wound closure compared to patients who received primary flap reconstruction. Additionally, we propose an algorithm for an interdisciplinary surgical therapy of soft-tissue sarcomas regarding resection and reconstruction and present two problematic cases to emphasize the complexity of surgical sarcoma therapy.
CRIS-Team Scopus Importer:2023-03-10
Keywords: extremity soft-tissue sarcomas; reconstructive surgery; surgical resection

Interdisciplinary Treatment of Breast Cancer After Mastectomy With Autologous Breast Reconstruction Using Abdominal Free Flaps in a University Teaching Hospital—A Standardized and Safe Procedure - Steiner, Dominik; Horch, Raymund E.; Ludolph, Ingo; Schmitz, Marweh; Beier, Justus; Arkudas, Andreas (Frontiers in Oncology, 2020)
Background: Breast cancer is the most common malignancy in women. The interdisciplinary treatment is based on the histological tumor type, the TNM classification, and the patient's wishes. Following tumor resection and (neo-) adjuvant therapy strategies, breast reconstruction represents the final step in the individual interdisciplinary treatment plan. Although manifold flaps have been described, abdominal free flaps, such as the deep inferior epigastric artery perforator (DIEP) or the muscle-sparing transverse rectus abdominis myocutaneous (ms-TRAM) flap, are the current gold standard for autologous breast reconstruction. This retrospective study focuses on the safety of autologous breast reconstruction upon mastectomy using abdominal free flaps. Methods: From April 2012 until December 2018, 193 women received 217 abdominal free flaps for autologous breast reconstruction at the University Hospital of Erlangen. For perforator mapping, we performed computed tomography angiography (CTA). Venous anastomosis was standardized using a ring pin coupler system, and flap perfusion was assessed with fluorescence angiography. A retrospective analysis was performed based on medical records, the surgery report, and follow-up of outpatient course. Results: In most cases, autologous breast reconstruction was performed as a secondary reconstructive procedure after mastectomy and radiotherapy. In total, 132 ms1-TRAM, 23 ms2-TRAM, and 62 DIEP flaps were performed with 21 major complications (10%) during hospital stay including five free flap losses (2.3%). In all cases of free flap loss, we found an arterial thrombosis as the main cause. In 24 patients a bilateral breast reconstruction was performed without free flap loss. The majority of free flaps (96.7%) did not need additional supercharging or turbocharging to improve venous outflow. Median venous coupler size was 2.5 mm (range, 1.5–3.5 mm). Conclusion: Using CTA, intraoperative fluorescence angiography, titanized hernia meshes for rectus sheath reconstruction, and venous coupler systems, autologous breast reconstruction with DIEP or ms-TRAM free flaps is a safe and standardized procedure in high-volume microsurgery centers.
CRIS-Team Scopus Importer:2020-04-10
Keywords: breast reconstruction; CTA; DIEP; interdisciplinary; ms-TRAM; venous coupler

Intradermal and transdermal absorption of beta-naphthylamine and N-Phenyl-beta-naphthylamine in a viable human skin model - Mini Vijayan, Suvarna; Baierl, Moritz; Göen, Thomas; Horch, Raymund E.; Ludolph, Ingo; Drexler, Hans; Kilo, Sonja (Toxicology in Vitro, 2024)
Technical products containing N-Phenyl-beta-naphthylamine (PBNA) are contaminated with beta-naphthylamine (BNA), a known carcinogen. Both amines penetrate the skin to different degrees, but little is known about their dermal-depot formation. This study investigated the dermal penetration of PBNA and its degradation product BNA using a viable human-skin model. PBNA (259 μg) or BNA (0.52 μg) in n-hexane and industrial grease were applied to freshly excised human skin (n = 6, 0.64 cm2) for 2-72 h. After temporary/continuous and single/repeated exposure, samples were taken (stratum corneum, epidermis/dermis, receptor fluid) and analyzed for their amine content by GC–MS. Continuous exposure led to a PBNA dermal depot of ∼47 μg/cm2 over 72 h. Temporary applications also resulted in lower but consistent PBNA dermal depots. A single 2-h application resulted in a dermal depot of ∼16 μg/cm2 after 72 h, while this was ∼25 μg/0.64 cm2 with repeated applications. BNA behaved differently; with repeated 2-h applications, intradermally retained BNA initially increased 3–6 fold, then dropped to ∼200–250 ng/cm2. This incomplete decline upon repeated short-term exposure to PBNA suggests that a BNA dermal depot is formed either due to contamination of PBNA with BNA or to enzymatic conversion of PBNA to BNA. Additionally, PBNA dermal depots were saturable under the given conditions. These findings highlight the importance of understanding the dermal-exposure dynamics of potential carcinogenic compounds in industrial settings.
CRIS-Team Scopus Importer:2024-10-18
Keywords: beta-naphthylamine; Dermal depot; Intradermal penetration; N-Phenyl-beta-naphthylamine; Transdermal absorption; Viable skin

Intraoperative Blood Flow Analysis of Free Flaps with Arteriovenous Loops for Autologous Microsurgical Reconstruction - Geierlehner, Alexander; Horch, Raymund E.; Ludolph, Ingo; Lang, Werner; Rother, Ulrich; Meyer, Alexander; Arkudas, Andreas (Journal of Clinical Medicine, 2023)
Background: Arteriovenous (AV) loops help to overcome absent or poor-quality recipient vessels in highly complex microvascular free flap reconstruction cases. There are no studies on blood flow and perfusion patterns. The purpose of this study was to evaluate and compare intraoperative hemodynamic characteristics of AV loops followed by free tissue transfer for thoracic wall and lower extremity reconstruction. Methods: this prospective clinical study combined Transit-Time Flowmetry and microvascular Indocyanine Green Angiography for the assessment of blood flow volume, arterial vascular resistance and intrinsic transit time at the time of AV loop construction and on the day of free flap transfer. Results: A total of 11 patients underwent AV loop creation, of whom five required chest wall reconstruction and six required reconstruction of the lower extremities. In seven of these cases, the latissimus dorsi flap and in four cases the vertical rectus abdominis myocutaneous (VRAM) flap was used as a free flap. At the time of loop construction, the blood flow volume of AV loops was 466 ± 180 mL/min, which increased to 698 ± 464 mL/min on the day of free tissue transfer (p > 0.1). After free flap anastomosis, the blood flow volume significantly decreased to 18.5 ± 8.3 mL/min (p < 0.001). There was no significant difference in blood flow volume or arterial vascular resistance between latissimus dorsi and VRAM flaps, nor between thoracic wall and lower extremity reconstruction. However, a significant correlation between the flap weight and the blood flow volume, as well as to the arterial vascular resistance, was found (p < 0.05). Conclusion: This is the first study to perform intraoperative blood flow and hemodynamic measurements of AV loops followed by free tissue transfer. Our results show hemodynamic differences and contribute to deeper understanding of the properties of AV loops for free flap reconstruction.
CRIS-Team Scopus Importer:2023-12-22
Keywords: ICG fluoroscopy; interdisciplinary plastic surgery; microsurgery; plastic surgery; reconstructive surgery; surgical innovation

Intraoperative flap design using ICG monitoring of a conjoined fabricated anterolateral thigh/tensor fasciae latae perforator flap in a case of extensive soft tissue reconstruction at the lower extremity - Bührer, Gregor; Taeger, Christian; Ludolph, Ingo; Horch, Raymund E.; Beier, Justus (Microsurgery, 2016)
In this report, we present a case of the use of a conjoined fabricated free anterolateral thigh (ALT)/tensor fascia latae (TFL) perforator flap for reconstruction of the lower extremity with intraoperative flap design using intraoperative indocyanine green (ICG) monitoring. The flap was used for reconstruction of a 16 cm × 28 cm sized defect of the lower leg in a 24-year-old man. The defect was caused by a third degree open fracture to the tibia. Upon dissection of the ALT perforators, ICG monitoring showed that both dominant ALT perforators did not yield a sufficient perforasome ( 16 cm × 17 cm) for the larger flap needed. An adjacent TFL perforator also supplied a large perforasome ( 15 cm × 11 cm), so a conjoined fabricated flap was harvested and transplanted to cover an extensive lower leg defect. The artery of the TFL perforator pedicle was being in-flap anastomosed to a side branch of the ALT pedicle. Postoperative course was uneventful and there were no complications. Length of follow-up was 6 months, aesthetic and functional outcome was good. The patient was very satisfied with the aesthetic outcome. Both legs were fully mobile after intensive physiotherapy for the reconstructed leg. The leg where the flap had been harvested showed full strength in knee joint flexion. This case could show that identification of the supplying vessels may be possible by ICG monitoring. © 2015 Wiley Periodicals, Inc. Microsurgery 36:684-688, 2016.
EVALuna2:15607

Is Instillational Topical Negative Pressure Wound Therapy in Peri-Prosthetic Infections of the Breast Effective? A Pilot Study - Grüner, Johanna; Horch, Raymund E.; Geierlehner, Alexander; Müller-Seubert, Wibke; Cai, Aijia; Arkudas, Andreas; Ludolph, Ingo (Journal of Personalized Medicine, 2022)
Peri-prosthetic breast infections pose a risk of severe complications after breast implant surgery. The need to remove the breast implant, control the infection and perform additional surgical procedures are the consequences. Reimplantation of an alloplastic implant is only appropriate after an infection-free interval. In this retrospective cohort study, we investigated the effectiveness of negative pressure wound treatment with instillation and dwell time (NPWTi-d) on peri-prosthetic breast infections in combination with implant removal and antibiotic therapy. Twelve patients treated with NPWTi-d due to breast implant infection were included in the study. The bacterial burden was analyzed using wound swabs before and after NPWTi-d. Additionally, laboratory values were determined before NPWTi-d and immediately before wound closure. A total of 13 peri-prosthetic breast infections in 12 patients were treated using implant removal and NPWTi-d. In 76.9% (n = 10) of the cases, the patients had undergone alloplastic breast reconstruction following cancer-related mastectomy, whereas 23.1% (n = 3) of the patients had undergone breast augmentation for cosmetic reasons. The bacterial burden in the breast pocket decreased statistically significant after implant removal and NPWTi-d. No shift from Gram-positive to Gram-negative bacteria was observed. Inflammatory markers rapidly decreased following treatment. NPWTi-d had a positive impact on the healing process after peri-prosthetic breast infections, leading to a decrease in bacterial burden within the wounds and contributing to uneventful healing. Therefore, secondary reimplantation of breast prostheses might be positively influenced when compared to conventional implant removal and simple secondary closure. Further studies are required to conclusively establish the beneficial long-term effects of using NPWTi-d for the treatment of peri-prosthetic breast infections.
CRIS-Team WoS Importer:2023-01-06

Is there a Rationale for Autologous Breast Reconstruction in Older Patients? A Retrospective Single Center Analysis of Quality of life, Complications and Comorbidities after DIEP or ms-TRAM Flap Using the BREAST-Q - Ludolph, Ingo; Horch, Raymund E.; Harlander, Marina; Arkudas, Andreas; Bach, Alexander D.; Kneser, Ulrich; Schmitz, Marweh; Taeger, Christian; Beier, Justus (BREAST J, 2015)
Autologous breast reconstruction with the deep inferior epigastric perforator (DIEP) or muscle-sparing transverse rectus abdominis myocutaneous (ms-TRAM) flap is a common method in the majority of patients after mastectomy. Because of an increased perioperative risk profile the benefit in older patients is questionable. To assess the postoperative quality of life and peri- and post-operative complications of older compared to younger patients is the aim of this retrospective study. In a retrospective analysis 39 older (i.e. >60 years) and 140 younger patients (i.e. <60 years) with autologous breast reconstruction in the Department of Plastic Surgery at the University Hospital of Erlangen-Nuernberg were surveyed at least 6 month postoperative using the BREAST-Q questionnaire. Correlations were generated between comorbidities and complications. Significant differences were observed regarding hospitalization, pre-existing diseases and the choice of DIEP versus ms-TRAM flaps. Parameters such as major and minor complications, bulging or hernia and risk factors (e.g. smoking or obesity) showed no significant differences. The results of the questionnaire parameters showed no significant difference between both groups, revealing high satisfaction with the aesthetic result and an improvement in quality of life independent of age. Autologous breast reconstruction after mastectomy generates a gain in quality of life and shows a good to excellent overall satisfaction in older as well as younger patients. Despite a longer hospitalization and a different risk profile there were no significant differences regarding minor and major complications in the postoperative course. Hence autologous breast reconstruction for older patients is justified and should be taken into consideration.
EVALuna2:15594

Leaving the perfusion zones? Individualized flap design in 100 free DIEP and ms-TRAM flaps for autologous breast reconstruction using indocyanine green angiography - Ludolph, Ingo; Bettray, Dominik; Beier, Justus; Horch, Raymund E.; Arkudas, Andreas (Journal of Plastic Reconstructive and Aesthetic Surgery, 2021)
Background: There is still no consensus regarding the ideal zoning in abdominal-based autologous breast reconstruction using free DIEP or ms-TRAM flaps. In particular, the perfusion pattern of the flap according to the number of perforators used and their location remains controversial. In this study, the perfusion of free DIEP and ms-TRAM flaps is assessed intraoperatively and analyzed with regard to different perfusion patterns. Methods: A retrospective analysis of 100 free flaps for breast reconstruction was performed. Following complete flap harvest, we used indocyanine green angiography for perfusion analysis. By applying two different contour levels, DIEP flaps with lateral or medial perforators and ms-TRAM flaps were assessed for their respective perfusion patterns. Results: No statistically significant differences were found in the size of the perfusion area between the different flap types when applying the contour level of 20% (p >0.05). For the contour level of 30%, however, statistically significant differences were found between DIEP flaps with medially or laterally located perforators (p = 0.038). Laterally or medially located perforators in DIEP flaps showed no significant differences in their ability to cross the midline (contour level 20%, p = 0.068; contour level 30%, p = 0.058). Conclusion: Considering the variability of the perfusion of the abdominal wall and the high sensitivity of indocyanine green angiography for their detection, the abdominal zonings play a minor role. By using intraoperative indocyanine green angiography, a precise and patient-specific free flap surgery for autologous breast reconstruction is possible independent of perforator location.
CRIS-Team Scopus Importer:2021-09-17
Keywords: Breast reconstruction; DIEP; ICG; Indocyanine green; Perfusion; Zone

Less is more – retrospective comparison of shoulder strength and range of motion between conventional and muscle-sparing harvesting technique of a latissimus dorsi flap - Müller-Seubert, Wibke; Scheibl, Karsten; Bührer, Gregor; Möbius, Cornelia; Ludolph, Ingo; Horch, Raymund E.; Arkudas, Andreas (Journal of Plastic Reconstructive and Aesthetic Surgery, 2021)
Background: The muscle-sparing latissimus dorsi flap poses an alternative to the conventional latissimus dorsi flap when a defect requires a smaller flap volume with a long vascular pedicle. The aim of the study was to analyze the functional outcome following muscle-sparing versus conventional harvest of a latissimus dorsi flap. Material and Methods: Patients who received a muscle-sparing latissimus dorsi muscle flap transplantation (group 1) and patients with a complete latissimus dorsi muscle flap harvest (group 2) for defect reconstruction at the University Hospital of Erlangen between 2007 and 2016 were examined. The evaluation included a physical examination with the measurement of strength and range of motion of the shoulder of both the donor side as well as the nonoperated side. Furthermore, the DASH score was evaluated. Additionally, patients in group 1 received a neurophysiological examination. Results: The DASH score did not show statistically significant differences between both groups. Both strength (p = 0.031) and range of motion (p<0.05) of the shoulder of the donor side were statistically significantly lower than the nonoperated side in group 2, while no difference was found in group 1. The neurophysiological examination in group 1 showed a reduced nerve conduction velocity of the donor side as compared to the nonoperated side in most patients (60% and n = 3). Conclusion: Harvesting the muscle-sparing latissimus dorsi flap leads to less functional impairments of the shoulder than harvesting the complete latissimus dorsi flap.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Defect reconstruction; Functional impairment; Latissimus dorsi flap; Muscle sparing latissimus dorsi flap

Limb salvage procedure in immunocompromised patients with therapy-resistant leg ulcers-The value of ultra-radical debridement and instillation negative-pressure wound therapy - Geierlehner, Alexander; Horch, Raymund E.; Müller-Seubert, Wibke; Arkudas, Andreas; Ludolph, Ingo (International Wound Journal, 2020)
The purpose of this study was to analyse the outcome of our established triple treatment strategy in therapy-resistant deep-thickness chronic lower leg ulcers. This limb salvage approach consists of ultra-radical surgical debridement, negative-pressure wound therapy (NPWT) with or without instillation, and split-thickness skin grafting. Between March 2003 and December 2019, a total of 16 patients and 24 severe cases of lower leg ulcers were eligible for inclusion in this highly selective population. A total of seven patients received immunosuppressive medication. Complete wound closure was achieved in 25% and almost 90% of included lower leg ulcer cases after 3 and 24 months of our triple treatment strategy, respectively. The overall limb salvage rate was 100%. Bacterial colonisation of these wounds was significantly reduced after multiple surgical debridements and NPWT. Fasciotomy and radical removal of devitalised tissue such as deep fascia, tendons, and muscles combined with NPWT showed promising results in terms of the overall graft take rate. This treatment strategy was considered as last resort for limb salvage in such a critically ill and immunocompromised patient population. Surgeons should be aware of its efficacy and consider the triple treatment strategy especially if no other limb salvage option remains.
CRIS-Team Scopus Importer:2020-07-03
Keywords: chronic leg ulcer; negative-pressure wound therapy; skin transplantation; ultra-radical debridement

Microcirculation Evaluated by Intraoperative Fluorescence Angiography after Tibial Bypass Surgery - Rother, Ulrich; Lang, Werner; Horch, Raymund E.; Ludolph, Ingo; Meyer, Alexander; Regus, Susanne (Annals of Vascular Surgery, 2017)
Intact microperfusion of the foot in the critical ischemic limb remains a crucial condition for ulcer healing. Aim of this clinical study was to evaluate the immediate effect of tibial bypass surgery on the microcirculation by usage of fluorescence angiography.Prospective analysis of 33 patients presenting with critical limb ischemia (Rutherford IV-VI) undergoing tibial bypass surgery was performed. Macroperfusion was investigated by measurement of ankle-brachial index. For assessment of microperfusion, intraoperative fluorescence angiography (SPY Elite, NOVADAQ) was undertaken during general anesthesia immediately before and after operation. For each investigation, a fluorescence dye (Indocyanine green) with an amount of 0.1 mg/kg was administered intravenously. Follow-up investigations were performed to assess the clinical outcome.The mean follow-up time was 8.28 (±4.46) months. The parameters Ingress (IN) and Ingress rate (InR) of the fluorescence dye representing the microcirculation showed a significant improvement to preoperative values and correlated with the ankle-brachial index significantly. Furthermore, a significant difference between the individual improvement of the microcirculation parameters (preoperative-postoperative) between patients with postoperative clinical improvement (wound healing, absence of rest pain) and those without could be demonstrated (InR: P = 0.039, IN: P = 0.036).The parameters IN and InR significantly reproduced the postoperative improvement of the microcirculation. An increased ankle-brachial index significantly correlated with increased microcirculation parameters. A better clinical outcome was found in those patients who had a higher relative improvement of microcirculation postoperatively.
EVALuna2:15278

Negative Pressure Wound Therapy Combined With Instillation for Sternoclavicular Joint Infection - Schreiner, Waldemar; Ludolph, Ingo; Dudek, Wojciech; Horch, Raymund E.; Sirbu, Horia (Annals of Thoracic Surgery, 2020)
Background: There is no consensus on the management of spontaneous sternoclavicular joint infection (SCJI). Negative pressure wound therapy (NPWT) has been widely accepted for SCJI. We reviewed our experience with the management of this condition comparing NPWT alone and NPWT combined with instillation and dwell time. Methods: We retrospectively analyzed the data of patients with spontaneous SCJI treated in our thoracic unit. Results: From March 2008 to October 2019, 27 patients (21 men and 6 women) underwent NPWT combined with muscle flap transfer after necrosectomy and chest wall resection for SCJI. The median age was 57.1 years (range, 35 to 85). Depending on management, the patients were divided into two groups: 16 patients with NPWT in group 1, and 11 patients with NPWT combined with instillation and dwell time in group 2. The severity of SCJI, extent of chest wall resection, and type of muscle flap were not significantly different (P = .35, P = .858, P = .705, respectively). Median duration of hospital stay and NPWT were shorter in group 2 (30 vs 25 days, and 20 vs 16 days, respectively). The required wound dressing changes were significantly lower in group 2 (P = .008). Statistical trend to higher bacterial eradication in group 2 was noted (P = .093). Postoperative complications including SCJI recurrence, wound seroma, and dehiscence were not significantly different between groups (P = .269). Conclusions: The NPWT combined with instillation and dwell time appears a useful strategy in patients with SCJI, leading to higher incidence of bacterial eradication and shorter wound care.
CRIS-Team Scopus Importer:2020-10-30

Novel imaging methods reveal positive impact of topical negative pressure application on tissue perfusion in an in vivo skin model - Müller-Seubert, Wibke; Roth, Sascha; Hauck, Theresa; Arkudas, Andreas; Horch, Raymund E.; Ludolph, Ingo (International Wound Journal, 2021)
The influence of topical negative pressure application (TNPA) on tissue perfusion still remains controversial. TNPA was applied for 30 minutes on intact skin of 21 healthy participants. Measurements of tissue oxygen saturation and tissue temperature as signs of tissue perfusion were performed before application of the TNPA, directly after removal of the TNPA and 5, 10, 15, 20, and 30 minutes after removal of the dressing using the near infrared imaging (NIRI) and a thermal imaging camera. Tissue oxygen saturation showed an increase from 67.7% before applying the TNPA to 76.1% directly after removal of TNPA, followed by a decrease of oxygen saturation 30 minutes after removal of TNPA. The measured temperature of the treated skin area increased from 32.1 degrees C to 36.1 degrees C after removal of TNPA with a consecutive decrease of the temperature 30 minutes after removal. TNPA resulted in both a higher tissue oxygen saturation and a higher skin temperature after 30 minutes compared to the beginning. TNPA increases both tissue oxygen saturation and skin temperature as sign of an increase of tissue perfusion. NIRI and thermal imaging proved to be useful for measuring changes in tissue perfusion.
CRIS-Team WoS Importer:2021-06-25

Operating on the Edge? Body Contouring Procedures in Patients with Body Mass Index Greater 35 - Hauck, Theresa; Schmitz, Marweh; Horch, Raymund E.; Arkudas, Andreas; Boos, Anja; Ludolph, Ingo; Cai, Aijia (Obesity Surgery, 2019)
Background Body contouring surgery after massive weight loss was shown to ameliorate the patient's quality of life and to enhance physical and psychological well-being. However, numerous patients are still obese when presenting for body contouring surgery, not able to lose additional weight for various reasons. Data regarding general feasibility, outcome, and postoperative complications in obese patients is rare. The aim of this study was to investigate the outcome in body contouring procedures in obese patients.
CRIS-Team WoS Importer:2019-05-24

Penile reconstruction with dermal template and vacuum therapy in severe skin and soft tissue defects caused by Fournier's gangrene and hidradenitis suppurativa - Ludolph, Ingo; Titel, Torsten; Beier, Justus; Dragu, Adrian; Schmitz, Marweh; Wullich, Bernd; Horch, Raymund E. (International Wound Journal, 2016)
The aim of this article is to improve the treatment of patients with complete skin loss of the penile shaft after Fournier's gangrene or hidradenitis suppurativa using modern biomatrices and topical negative pressure therapy. From January 2010 to December 2011, three patients with Fournier's gangrene or hidradenitis suppurativa were treated. After initial radical debridements, topical negative pressure therapy was applied for wound stabilisation. After that dermal templates (acellular dermal matrix) were used to achieve early healing and topical negative pressure-dressing in a special setting or a special foam compression bandage was used together with a urinary catheter. After integration of the dermal template, a split-thickness skin graft is used for coverage and again secured with a circular total negative pressure-dressing. In all cases, the split-thickness skin grafts healed very well applying this therapy concept. The patients were very satisfied with the functional as well as with the aesthetic outcome. We suggest a new method of staged reconstruction to successfully preserve the functionality of the penis after complete loss of the skin and soft tissue of the penile shaft using modern biomatrices and topical negative pressure therapy.
EVALuna2:15559

Personalized reconstruction of genital defects in complicated wounds with vertical rectus abdominis myocutaneous flaps including urethral neo-orifice - Horch, Raymund E.; Ludolph, Ingo; Arkudas, Andreas; Cai, Aijia (Journal of Personalized Medicine, 2021)
Non-healing extensive wounds in the perineal region can lead to severe soft tissue infections and disastrous complications, which are not manageable with conservative measures. Specifically in recurrent or advanced pelvic malignancies, irradiation often leads to extensive scarring and wound breakdown, resulting in significant soft tissue defects during surgical tumor excision. Among several surgical options to reconstruct the perineum, the transpelvic vertical rectus abdominis myocutaneous (VRAM) flap has proven to be one of the most reliable methods. Specific modifications of this flap allow an individualized procedure depending on the patient’s needs. We modified this technique to include the urethral orifice into the skin paddle of VRAM flaps in three patients as a novel option to circumvent urinary diversion and maintain an acceptable quality of life.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Neourethra; Perineal reconstruction; Urethral reconstruction; VRAM flap

PGC-1α regulates autophagy to promote fibroblast activation and tissue fibrosis - Zhang, Yun; Shen, Lichong; Zhu, Honglin; Dreissigacker, Katja; Distler, Diana; Zhou, Xiang; Györfi, Andrea-Hermina; Bergmann, Christina; Meng, Xianyi; Dees, Clara; Trinh-Minh, Thuong; Ludolph, Ingo; et al. (Annals of the Rheumatic Diseases, 2020)
Objectives Coactivators are a heterogeneous family of transcriptional regulators that are essential for modulation of transcriptional outcomes and fine-tune numerous cellular processes. The aim of the present study was to evaluate the role of the coactivator peroxisome proliferator-activated receptor gamma coactivator-1α (PGC-1α) in the pathogenesis of systemic sclerosis (SSc). Methods Expression of PGC-1α was analysed by real-time PCR, western blot and immunofluorescence. Modulation of autophagy was analysed by reporter studies by expression of autophagy-related genes. The effects of PGC-1α knockdown on collagen production and myofibroblast differentiation were analysed in cultured human fibroblasts and in two mouse models with fibroblast-specific knockout of PGC-1α. Results The expression of PGC-1α was induced in dermal fibroblasts of patients with SSc and experimental murine fibrosis. Transforming growth factor beta (TGFβ), hypoxia and epigenetic mechanisms regulate the expression of PGC-1α in fibroblasts. Knockdown of PGC-1α prevented the activation of autophagy by TGFβ and this translated into reduced fibroblast-to-myofibroblast differentiation and collagen release. Knockout of PGC-1α in fibroblasts prevented skin fibrosis induced by bleomycin and by overexpression of a constitutively active TGFβ receptor type I. Moreover, pharmacological inhibition of PGC-1α by SR18292 induced regression of pre-established, bleomycin-induced skin fibrosis. Conclusion PGC-1α is upregulated in SSc and promotes autophagy to foster TGFβ-induced fibroblast activation. Targeting of PGC-1α prevents aberrant autophagy, inhibits fibroblast activation and tissue fibrosis and may over therapeutic potential.
CRIS-Team Scopus Importer:2020-09-11
Keywords: fibroblasts; systemic sclerosis; treatment

Pilot Assessment of the Angiosome Concept by Intra-operative Fluorescence Angiography After Tibial Bypass Surgery - Rother, Ulrich; Lang, Werner; Horch, Raymund E.; Ludolph, Ingo; Meyer, Alexander; Gefeller, Olaf; Regus, Susanne (European Journal of Vascular and Endovascular Surgery, 2018)
OBJECTIVES: The "angiosome" concept as a model for decision making in revascularisation of patients with critical limb ischaemia (CLI) has been subject to lively discussion in recent years. The aim of this prospective pilot study was to use intra-operative fluorescence angiography to provide further data on the angiosome concept on the level of microcirculation after tibial bypass surgery. DESIGN, MATERIALS, AND METHODS: This was a prospective analysis of 40 patients presenting with CLI Rutherford stage IV to VI before and after tibial bypass surgery. The macrocirculation was measured by the ankle brachial index. Skin microcirculation was assessed by intra-operative fluorescence angiography. The alteration of microcirculation was compared in direct and indirect revascularised angiosomes. Clinical follow-up investigations were performed and the wound healing rate was compared between the different revascularisation methods. RESULTS: Cumulated microcirculation parameters showed a significant improvement after surgery (ingress, ingress rate p<.001). Likewise, general microcirculatory improvement was observed in each foot angiosome after revascularisation, regardless of the tibial artery revascularised. Furthermore, a comparison of the direct (DR) and the indirect revascularised (IR) angiosomes did not show a significant difference concerning the improvement of microcirculation (difference DR-IR, ingress: 1.69, 95% CI 71.73-75.11; ingress rate: 0.08, 95% CI -12.91 to 13.07). The wound healing rate was similar in both groups, although the time to wound healing was faster by on average 2.5 months in the DR group (p=.083). CONCLUSION: Microcirculatory improvement was seen over the whole foot after tibial bypass. Therefore, fluorescence angiography is a promising tool to evaluate the angiosome concept in future larger studies. Clinicaltrials.gov: NCT03012750.
EVALuna2:35687

Plastic reconstructive microsurgery in the elderly patient - Consensus statement of the German Speaking Working Group for Microsurgery of the Peripheral Nerves and Vessels - Ludolph, Ingo; Lehnhardt, Marcus; Arkudas, Andreas; Kneser, Ulrich; Pierer, Gerhard; Harder, Yves; Horch, Raymund E. (Handchirurgie, Mikrochirurgie, Plastische Chirurgie, 2018)
During the last two decades, understanding and experience of microsurgical reconstruction have increased. This is linked to improved instruments and technical devices, as well as to the increased number of available donor sites for microvascular flap transfer. If the indication is appropriate, it is now possible to perform personalised, safe and successful microsurgical reconstructions, almost independently of the patients' age. Despite these constant developments, there is little specific literature on microsurgery related to the specific problems of the elderly patient. During two consensus workshops organised by the DAM (German Speaking Working Group for Microsurgery of the Peripheral Nerves and Vessels), the latest findings and experience with microsurgical reconstruction in the elderly patient were presented by a group of experts and current recommendations were formulated. On the basis of these consensus workshops and the current literature, this article discusses important issues in this area.
EVALuna2:211479

Plastisch-chirurgische Rekonstruktion bei ausgedehnten Beckenbodendefekten nach onkologischer Chirurgie - Horch, Raymund E.; Arkudas, Andreas; Ludolph, Ingo; Cai, Aijia; Mulica, Markus (Coloproctology, 2020)
Due to the increasing further development of oncological surgical procedures, in particular extralevatory rectal extirpation in combination with neoadjuvant radiation of the pelvis, the risk of local recurrence of rectal cancer (LRRC) could be reduced to 5–10%. Curative treatment of LRRC necessitates a complete resection with microscopically tumor-free borders (R0); however, the oncologically meaningful radical surgery frequently leads to substantial structural and functional pelvic floor and perineal defects. The resulting mostly irradiated wound cavity after abdominoperineal extirpation (APE) or pelvic exenteration has a high risk of wound healing disorders after primary closure. For primary and also recurrent rectal and anal cancer it was shown that interdisciplinary one-stage reconstructive plastic surgery of the pelvic floor and the perineum and also the vagina, e.g. with a transpelvic vertical rectus abdominis myocutaneous (VRAM) flap, can improve the quality of life and reduce hospitalization times. Even in the long-term course, protracted secondary wound healing disorders can be minimized or avoided using this method.
CRIS-Team Scopus Importer:2020-11-20
Keywords: Interdisciplinary surgery; Pelvic exenteration; Pelvic floor reconstruction; Rectal cancer; VRAM-flap

Poly(ADP-ribose) polymerase-1 regulates fibroblast activation in systemic sclerosis - Zhang, Yun; Pötter, Sebastian; Chen, Chih-Wei; Liang, Ruifang; Gelse, Kolja; Ludolph, Ingo; Horch, Raymund E.; Distler, Oliver; Schett, Georg; Distler, Jörg; Dees, Clara (Annals of the Rheumatic Diseases, 2018)
OBJECTIVES: The enzyme poly(ADP-ribose) polymerase-1 (PARP-1) transfers negatively charged ADP-ribose units to target proteins. This modification can have pronounced regulatory effects on target proteins. Recent studies showed that PARP-1 can poly(ADP-ribosyl)ate (PARylate) Smad proteins. However, the role of PARP-1 in the pathogenesis of systemic sclerosis (SSc) has not been investigated. METHODS: The expression of PARP-1 was determined by quantitative PCR and immunohistochemistry. DNA methylation was analysed by methylated DNA immunoprecipitation assays. Transforming growth factor-β (TGFβ) signalling was assessed using reporter assays, chromatin immunoprecipitation assays and target gene analysis. The effect of PARP-1 inactivation was investigated in bleomycin-induced and topoisomerase-induced fibrosis as well as in tight-skin-1 (Tsk-1) mice. RESULTS: The expression of PARP-1 was decreased in patients with SSc, particularly in fibroblasts. The promoter of PARP-1 was hypermethylated in SSc fibroblasts and in TGFβ-stimulated normal fibroblasts. Inhibition of DNA methyltransferases (DNMTs) reduced the promoter methylation and reactivated the expression of PARP-1. Inactivation of PARP-1 promoted accumulation of phosphorylated Smad3, enhanced Smad-dependent transcription and upregulated the expression of TGFβ/Smad target genes. Inhibition of PARP-1 enhanced the effect of TGFβ on collagen release and myofibroblast differentiation in vitro and exacerbated experimental fibrosis in vivo. PARP-1 deficiency induced a more severe fibrotic response to bleomycin with increased dermal thickening, hydroxyproline content and myofibroblast counts. Inhibition of PARylation also exacerbated fibrosis in Tsk-1 mice and in mice with topoisomerase-induced fibrosis. CONCLUSION: PARP-1 negatively regulates canonical TGFβ signalling in experimental skin fibrosis. The downregulation of PARP-1 in SSc fibroblasts may thus directly contribute to hyperactive TGFβ signalling and to persistent fibroblast activation in SSc.
EVALuna2:34150

Postbariatrische plastische Körperrekonstruktionen - Promny, Theresa; Ludolph, Ingo; Müller-Seubert, Wibke; Cai, Aijia; Promny, Dominik; Horch, Raymund E. (Die Chirurgie, 2024)
Massive weight loss following bariatric surgery is often accompanied by functional impairments due to the resulting excess skin and soft tissues. To achieve both functional reconstruction and restoration of the body silhouette, it is imperative to undergo body contouring surgery involving the strategic transposition of tissues. Several surgical techniques are available for the affected body regions and their application for treatment is determined by the unique circumstances specific to each patient. When conducted by skilled practitioners, postbariatric body reconstruction can be executed safely, leading to outcomes that are both functionally and esthetically satisfying, ultimately contributing to an enhanced quality of life for patients. This article provides the fundamental principles for patient selection, surgical preparation, treatment planning, surgical techniques and the postoperative care following bariatric surgery.
EVALuna2:574356

Projection Mapping for In-Situ Surgery Planning by the Example of DIEP Flap Breast Reconstruction - Martschinke, Jana; Klein, Vanessa; Kurth, Philipp; Engel, Klaus; Ludolph, Ingo; Hauck, Theresa; Horch, Raymund E.; Stamminger, Marc (Eurographics Workshop on Visual Computing for Biology and Medicine, 2021)
Nowadays, many surgical procedures require preoperative planning, mostly relying on data from 3D imaging techniques like computed tomography or magnetic resonance imaging. However, preoperative assessment of this data is carried out on the PC (using classical CT/MR viewing software) and not on the patient's body itself. Therefore, surgeons need to transfer both their overall understanding of the patient's individual anatomy and also specific markers and labels for important points from the PC to the patient only with the help of imaginative power or approximative measurement. In order to close the gap between preoperative planning on the PC and surgery on the patient, we propose a system to directly project preoperative knowledge to the body surface by projection mapping. As a result, we are able to display both assigned labels and a volumetric and view-dependent view of the 3D data in-situ. Furthermore, we offer a method to interactively navigate through the data and add 3D markers directly in the projected volumetric view. We demonstrate the benefits of our approach using DIEP flap breast reconstruction as an example. By means of a small pilot study, we show that our method outperforms standard surgical planning in accuracy and can easily be understood and utilized even by persons without any medical knowledge.

Quick and safe: why a k-wire-extension-block-fixation of a bony mallet finger is the favoured treatment - Stumpfe, Maximilian; Suffa, Nadine; Merkel, Pauline; Ludolph, Ingo; Arkudas, Andreas; Horch, Raymund E. (Archives of Orthopaedic and Trauma Surgery, 2024)
Introduction: Mallet fingers are the most common tendon injuries of the hand. Bony avulsion distal finger extensor tendon ruptures causing a mallet finger require special attention and management. In this monocentral study, we analyzed the clinical and individual outcomes succeeding minimal invasive k-wire extension block treatment of bony mallet fingers. Materials and methods: In a retrospective study, we sent a self-designed template and a QUICK-DASH score questionnaire to all patients, who were treated because of a bony mallet finger between 2009 and 2022 and fulfilled the inclusion criteria. A total of 244 requests were sent out. 72 (29.5%) patients participated in the study. Forty-five men and twenty-seven women were included. Results: 98.7% (n = 75) of the cases were successfully treated. Patients were highly satisfied with the treatment (median 8.0; SD ± 2.9; range 1.0–10.0). Based on the QUICK-DASH score, all patients showed no difficulties in daily life. The extent of avulsion did not influence the outcome. Conclusion: We conclude that the minimally invasive treatment of a bony mallet finger should be offered to every patient, because it is safe, fast, and reliable. Thus, we propose to perform extension-block pinning independently of the articular area.
CRIS-Team Scopus Importer:2024-03-08
Keywords: Bony extensor tendon rupture; Intervention; Kirschner-wire-fixation; Mallet finger; Mallet fracture

Rare Pseudotumor-like Hematoma at the Latissimus Dorsi Muscle Flap Donor Site: A Treatment Strategy Utilizing Negative Pressure Wound Therapy With Instillation and Dwell Time - Stumpfe, Maximilian C.; Horch, Raymund E.; Geierlehner, Alexander; Ludolph, Ingo (Wounds: A Compendium of Clinical Research and Practice, 2020)
INTRODUCTION: In reconstructive surgery, the latissimus dorsi (LD) muscle is known as a workhorse flap and is commonly used as a pedicled or free flap. Postoperative complications of a reconstructive procedure with an LD flap include seroma and hematoma formation at an early stage after LD transfer. Late-onset hematoma at the donor site are considered to be extremely rare postoperative complications; late, expanding pseudotumor-like hematoma can occur months or years after surgery. Shearing forces and poor coagulation are thought to be the primary reasons for these postoperative complications. CASE REPORTS: This report presents 2 cases of pseudotumors 12 and 29 years after LD transfer. Magnetic resonance imaging was performed prior to complete surgical excision. After surgical removal, patients received negative-pressure wound therapy with instillation and dwell time (NPWTi-d) for several days. After vacuum-assisted wound bed preparation, wound closure was performed with secondary sutures. CONCLUSIONS: The case report presented 2 incidences of rare late-onset pseudotumors many years after the initial LD reconstruction. To the authors' knowledge, this late-onset occurrence (ie, after 3 decades) has not been reported in the literature to date. If solidification of the late hematoma makes aspiration impossible, surgical intervention is required. Negative pressure wound therapy with instillation and dwell time potentially minimizes the wound size and reduces shear forces at the back donor-site.
CRIS-Team Scopus Importer:2021-04-19

Reconstruction of composite defects of the scalp and neurocranium-a treatment algorithm from local flaps to combined AV loop free flap reconstruction - Steiner, Dominik; Horch, Raymund E.; Eyüpoglu, Ilker Yasin; Buchfelder, Michael; Arkudas, Andreas; Schmitz, Marweh; Ludolph, Ingo; Beier, Justus; Boos, Anja (World Journal of Surgical Oncology, 2018)
BACKGROUND: Reconstruction of cranial composite defects, including all layers of the scalp and the neurocranium, poses an interdisciplinary challenge. Especially after multiple previous operations and/or radiation therapy, sufficient reconstruction is often only possible using microsurgical free flap transplantation. The aim of this study was to analyze the therapy of interdisciplinary cases with composite defects including the scalp and neurocranium. METHODS: From 2009 to 2017, 23 patients with 18 free flaps and 10 pedicled/local flaps were analyzed. First choices for free flaps were muscle flaps followed by fasciocutaneous flaps. RESULTS: Except for four patients, a stable coverage could be reached in the first operation. Three of these patients received a local scalp rotation flap in the first operation and needed an additional free flap because the local flap was no longer sufficient for coverage after wound healing deficiency or tumor relapse. The superficial temporal artery or external carotid artery served as recipient vessels. In special cases, venous grafts or an arteriovenous loop (AV loop) were used as extensions for the recipient vessels. CONCLUSIONS: In summary, an interdisciplinary approach with radical debridement of infected or necrotic tissue and the reconstruction of the dura mater are essential to reach a stable, long-lasting reconstructive result. Based on our experience, free flaps seem to be the first choice for patients after multiple previous operations and/or radiation therapy.
EVALuna2:211467

Reconstruction of Extensive Volar Finger Defects with Double Cross-Finger Flaps - Bührer, Gregor; Arkudas, Andreas; Ludolph, Ingo; Horch, Raymund E.; Taeger, Christian (Plastic and Reconstructive Surgery Global Open, 2016)
Cross-finger flaps still represent a viable option to reconstruct small- to medium-sized full-thickness finger defects but they are not commonly used if larger areas have to be covered. We present 2 cases showing a simple and pragmatic approach with homodigital double cross-finger flaps to reconstruct extensive volar finger soft-tissue defects. We observed very low donor-site morbidity and excellent functional and aesthetic outcomes. Furthermore, there is no need for microsurgical techniques or equipment when using this method. Although this case report only addresses volar defects, one might also think of applying this concept to dorsal defects using reversed double cross-finger flaps.
CRIS-Team Scopus Importer:2025-05-07

Reconstruction of oncological defects of the perianal region - Horch, Raymund E.; Ludolph, Ingo; Arkudas, Andreas (Coloproctology, 2021)
In addition to the progressive development of surgical oncological techniques for malignant tumors of the rectum, anal canal and vulva, reconstructive procedures after oncological interventions in the perianal region represent a cornerstone in the postoperative quality of life of patients. Modern treatment modalities for rectal cancer with neoadjuvant chemoradiotherapy increase the survival rate and simultaneously reduce the risk of local recurrence to 5-10%, especially by cylindrical extralevatory extirpation of the rectum. The price for increased surgical radicality and improved oncological safety is the acceptance of larger tissue defects. Simple suture closure of perineal wounds often does not primarily heal, resulting in wound dehiscence, surgical site infections and formation of chronic fistulas and sinuses. The interdisciplinary one-stage or two-stage reconstruction of the perianal region with well-vascularized tissue has proven to be a reliable procedure to prevent or control such complications.
CRIS-Team WoS Importer:2021-11-26

Reconstruction of oncological defects of the perianal region Rekonstruktion onkologischer Defekte der Perianalregion - Horch, Raymund E.; Ludolph, Ingo; Arkudas, Andreas (Chirurg, 2021)
In addition to the progressive development of surgical oncological techniques for malignant tumors of the rectum, anal canal and vulva, reconstructive procedures after oncological interventions in the perianal region represent a cornerstone in the postoperative quality of life of patients. Modern treatment modalities for rectal cancer with neoadjuvant chemoradiotherapy increase the survival rate and simultaneously reduce the risk of local recurrence to 5–10%, especially by cylindrical extralevatory extirpation of the rectum. The price for increased surgical radicality and improved oncological safety is the acceptance of larger tissue defects. Simple suture closure of perineal wounds often does not primarily heal, resulting in wound dehiscence, surgical site infections and formation of chronic fistulas and sinuses. The interdisciplinary one-stage or two-stage reconstruction of the perianal region with well-vascularized tissue has proven to be a reliable procedure to prevent or control such complications.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Abdominoperineal resection; Pelvic floor exenteration; Pelvic floor reconstruction; Perineal hernia; Wound infection

Response to the letter to the editor ‘Novel imaging methods reveal positive impact of topical negative pressure application on tissue perfusion in an in-vivo skin model’ - Müller-Seubert, Wibke; Roth, Sascha; Hauck, Theresa; Arkudas, Andreas; Horch, Raymund E.; Ludolph, Ingo (International Wound Journal, 2021)
CRIS-Team Scopus Importer:2021-09-17

Retrospective analysis of free temporoparietal fascial flap for defect reconstruction of the hand and the distal upper extremity - Müller-Seubert, Wibke; Horch, Raymund E.; Schmidt, Vanessa; Ludolph, Ingo; Schmitz, Marweh; Arkudas, Andreas (Archives of Orthopaedic and Trauma Surgery, 2020)
Introduction: Soft tissue reconstruction of the hand and distal upper extremity is challenging to preserve the function of the hand as good as possible. Therefore, a thin flap has been shown to be useful. In this retrospective study, we aimed to show the use of the free temporoparietal fascial flap in soft tissue reconstruction of the hand and distal upper extremity. Methods: We analysed the outcome of free temporoparietal fascial flaps that were used between the years 2007and 2016 at our institution. Major and minor complications, defect location and donor site morbidity were the main fields of interest. Results: 14 patients received a free temporoparietal fascial flap for soft tissue reconstruction of the distal upper extremity. Minor complications were noted in three patients and major complications in two patients. Total flap necrosis occurred in one patient. Conclusion: The free temporoparietal fascial flap is a useful tool in reconstructive surgery of the hand and the distal upper extremity with a low donor site morbidity and moderate rates of major and minor complications.
CRIS-Team Scopus Importer:2020-11-13
Keywords: Hand; Reconstruction; Temporoparietal fascial flap; Upper extremity

Retrospective cohort study of combined approach for trunk reconstruction using arteriovenous loops and free flaps - Arkudas, Andreas; Horch, Raymund E.; Regus, Susanne; Meyer, Alexander; Lang, Werner; Schmitz, Marweh; Boos, Anja; Ludolph, Ingo; Beier, Justus (Journal of Plastic Reconstructive and Aesthetic Surgery, 2017)
Defect reconstruction of the trunk can be performed using microsurgical free flap transplantation. In cases of missing or inappropriate recipient vessels, microsurgical defect reconstruction of the trunk can be achieved by combining free flaps with arteriovenous loops. Here we present our 5-year experience of trunk reconstruction using AV loops and free flaps in a retrospective evaluation. We analyzed 32 cases of trunk reconstruction using a combined approach of free flap transplantation and arteriovenous loops between 2011 and 2016 regarding postoperative complications and perioperative course. Twenty-one patients suffered from sternal defects, 4 from presacral defects, 3 patients presented with lateral chest wall defects, 2 patients suffered from lumbosacral defects, 1 patient had a gluteal defect and 1 patient a defect at the clavicle. In all cases, free flap transplantation and arteriovenous loop creation were performed in a two-stage procedure. There were 8 thromboses of the arteriovenous loops with 4 flap failures. Only 1 flap loss was located in the sternal region, whereas one presacral flap and both lumbosacral flaps were lost. Reconstruction of large soft tissue defects of the trunk by a combined approach with an arteriovenous loop creation and consecutive free flap transplantation represents a reliable procedure in ventral and posterior cranial localization, whereas in the caudal posterior region, AV loop thrombosis can occur. Therefore, to minimize flap loss, a two-stage procedure should be performed.
EVALuna2:15321

Size matters-in vitro behaviour of human fibroblasts on textured silicone surfaces with different pore sizes - Juia, Tolksdorf; Horch, Raymund E.; Grüner, Jasmin; Schmid, Rafael; Kengelbach-Weigand, Annika; Schubert, Dirk W.; Werner, Siegfried; Schneidereit, Dominik; Friedrich, Oliver; Ludolph, Ingo (Journal of Materials Science: Materials in Medicine, 2020)
Capsular contracture remains a challenge in plastic surgery and represents one of the most common postoperative complications following alloplastic breast reconstruction. The impact of the surface structure of silicone implants on the foreign body reaction and the behaviour of connective tissue-producing cells has already been discussed. The aim of this study was to investigate different pore sizes of silicone surfaces and their influence on human fibroblasts in an in vitro model. Four different textures (no, fine, medium and coarse texture) produced with the salt-loss technique, have been assessed in an in vitro model. Human fibroblasts were seeded onto silicone sheets and evaluated after 1, 4 and 7 days microscopically, with viability assay and gene expression analysis. Comparing the growth behaviour and adhesion of the fibroblasts on the four different textures, a dense cell layer, good adhesion and bridge-building ability of the cells could be observed for the fine and medium texture. Cell number and viability of the cells were increasing during the time course of experiments on every texture. TGFß1 was lowest expressed on the fine and medium texture indicating a trend for decreased fibrotic activity. For silicone surfaces produced with the salt-loss technique, we were able to show an antifibrotic effect of smaller sized pores. These findings underline the hypothesis of a key role of the implant surface and the pore size and pore structure in preventing capsular contracture.<br
Keywords: Silicone Surface; hand surgery; implants; Biocompatibility Studies

Specific features of ex-obese patients significantly influence the functional cell properties of adipose-derived stromal cells - Schmitz, Deborah; Robering, Jan Willem; Weisbach, Volker Günter; Arkudas, Andreas; Ludolph, Ingo; Horch, Raymund E.; Boos, Anja; Kengelbach-Weigand, Annika (Journal of Cellular and Molecular Medicine, 2022)
Adipose-derived stromal cells (ADSC) are increasingly used in clinical applications due to their regenerative capabilities. However, ADSC therapies show variable results. This study analysed the effects of specific factors of ex-obese patients on ADSC functions. ADSC were harvested from abdominal tissues (N = 20) after massive weight loss. Patients were grouped according to age, sex, current and maximum body mass index (BMI), BMI difference, weight loss method, smoking and infection at the surgical site. ADSC surface markers, viability, migration, transmigration, sprouting, differentiation potential, cytokine secretion, telomere length and mtDNA copy number were analysed. All ADSC expressed CD73, CD90, CD105, while functional properties differed significantly among patients. A high BMI difference due to massive weight loss was negatively correlated with ADSC proliferation, migration and transmigration, while age, sex or weight loss method had a smaller effect. ADSC from female and younger donors and individuals after weight loss by increase of exercise and diet change had a higher activity. Telomere length, mtDNA copy number, differentiation potential and the secretome did not correlate with patient factors or cell function. Therefore, we suggest that factors such as age, sex, increase of exercise and especially weight loss should be considered for patient selection and planning of regenerative therapies.
CRIS-Team Scopus Importer:2022-07-22
Keywords: adipose-derived stromal cells; bariatric surgery; body mass index; cell function; regenerative medicine

Staged reconstruction of challenging abdominal full thickness wounds caused by necrotizing fasciitis and complicated by occult rectal cancer-a rare combination - Schmitz, Marweh; Ludolph, Ingo; Horch, Raymund E. (International Journal of Colorectal Disease, 2016)
EVALuna2:15601

Successful free flap salvage upon venous congestion in bilateral breast reconstruction using a venous cross-over bypass: A case report - Steiner, Dominik; Horch, Raymund E.; Ludolph, Ingo; Arkudas, Andreas (Microsurgery, 2019)
Abdominal free flaps such as the muscle sparing transverse rectus abdominis myocutaneous (ms-TRAM) or deep inferior epigastric artery perforator (DIEP) flap represent the gold standard in autologous breast reconstruction. We describe a salvage procedure during bilateral free flap breast reconstruction due to insufficient venous drainage using a venous cross-over bypass. A 54-year-old woman with a thrombosis of the left subclavian port-system in the medical history was elected for simultaneous bilateral breast reconstruction with ms-TRAM and DIEP flaps. Intraoperatively, a venous congestion of the DIEP flap, which was connected to the left cranial internal mammary vessels, appeared. In the absence of sufficient ipsilateral venous recipient vessels, we performed a salvage procedure requiring a 15 cm small saphenous vein graft and presternal subcutaneous tunneling. The flap vein was anastomosed end-to-end with the contralateral caudal internal mammary vein using a coupler system. The postoperative course was uneventful and both flaps survived. We describe the cross-over venous emergency bypass as a useful tool in unexpected venous thrombosis during bilateral free flap breast reconstruction.
CRIS-Team Scopus Importer:2019-05-21

Temporarily Transfixation of the distal interphalangeal Joint in Mallet fingers - Suffa, Nadine; Merkel, Pauline; Horch, Raymund E.; Arkudas, Andreas; Ludolph, Ingo; Stumpfe, Maximilian Christoph (Handchirurgie, Mikrochirurgie, Plastische Chirurgie, 2021)
Zusammenfassung
CRIS-Team WoS Importer:2021-10-08

The influence of K-wire transfixation on proximalization of the first metacarpal after resection suspension interposition arthroplasty - Fritz, Niklas; Ludolph, Ingo; Arkudas, Andreas; Horch, Raymund E.; Cai, Aijia (Archives of Orthopaedic and Trauma Surgery, 2021)
Introduction: Osteoarthritis of the first carpometacarpal joint is a common degenerative disease and surgical treatment includes resection suspension interposition arthroplasty (RSIA) with or without temporary transfixation of the first metacarpal. One major drawback includes proximalization of the first metacarpal during the postoperative course. Specific data comparing different transfixation techniques in this context is sparse. Materials and methods: In this retrospective study, we measured the trapezial space ratio (TSR) in 53 hands before and after RSIA to determine the proximalization of the first metacarpal depending on the type of Kirschner (K)-wire transfixation. We, therefore, compared transfixation of the first metacarpal to the scaphoid with one K-wire (1K) to transfixation of the first metacarpal with two K-wires (2K), either to the carpus (2Ka), or to the second metacarpal (2Kb), or to both second metacarpal and carpus (2Kc). Results: While preoperative TSR did not differ between group 1K and 2K (p = 0.507), postoperative TSR was significantly higher in group 2K compared to 1K (p = 0.003). Comparing subgroups, postoperative TSR was significantly higher in group 2Kc than 1K (p = 0.046), while we found no significant difference comparing either group 2Ka or 2Kb to 1K (p = 0.098; p = 0.159). Neither did we find a significant difference within 2K subgroups, comparing group 2Ka and 2Kb (p = 0.834), 2Ka and 2Kc (p = 0.615), or 2Kb and 2Kc (p = 0.555). Conclusions: The results of our study suggest that transfixation with two K-wires should be preferred to transfixation with one K-wire after RSIA. Specifically, transfixation from first to second metacarpal and from first metacarpal to carpus resulted in least proximalization of the first metacarpal postoperatively.
CRIS-Team Scopus Importer:2021-02-05
Keywords: CMC1 joint; First metacarpal proximalization; K-wire transfixation; Osteoarthritis; Resection suspension arthroplasty; Saddle joint

The third dimension in perforator mapping—Comparison of Cinematic Rendering and maximum intensity projection in abdominal-based autologous breast reconstruction - Hauck, Theresa; Arkudas, Andreas; Horch, Raymund E.; Ströbel, Armin; May, Matthias; Binder, Johannes; Krautz, Christian; Ludolph, Ingo (Journal of Plastic Reconstructive and Aesthetic Surgery, 2022)
Background: Cinematic Rendering (CR) is a recently introduced post-processing three-dimensional (3D) visualization imaging tool. The aim of this study was to assess its clinical value in the preoperative planning of deep inferior epigastric artery perforator (DIEP) or muscle-sparing transverse rectus abdominis myocutaneous (MS-TRAM) flaps, and to compare it with maximum intensity projection (MIP) images. The study presents the first application of CR for perforator mapping prior to autologous breast reconstruction. Methods: Two senior surgeons independently analyzed CR and MIP images based on computed tomography angiography (CTA) datasets of 20 patients in terms of vascular pedicle characteristics, the possibility to harvest a DIEP or MS-TRAM flap, and the side of the flap harvest. We calculated inter- and intra-observer agreement in order to examine the accordance of both image techniques. Results: We observed a good inter- and intra-observer agreement concerning the type of flap and the side of the flap harvest. However, the agreement on the pedicle characteristics varies depending on the considered variable. Both investigators identified a significantly higher number of perforators with MIP compared with CR (observer 1, p<0.0001 and observer 2, p<0.0385). Conclusion: The current study serves as an explorative study, showing first experiences with CR in abdominal-based autologous breast reconstruction. In addition to MIP images, CR might improve the surgeon's understanding of the individual's anatomy. Future studies are required to compare CR with other 3D visualization tools and its possible effects on operative parameters.
CRIS-Team Scopus Importer:2022-03-11
Keywords: 3D visualization; Computed tomography angiography; DIEP; MS-TRAM

The Value of Negative-Pressure Wound Therapy and Flap Surgery in Hidradenitis Suppurativa – A Single Center Analysis of Different Treatment Options - Stumpfe, Maximilian; Horch, Raymund E.; Arkudas, Andreas; Cai, Aijia; Müller-Seubert, Wibke; Hauck, Theresa; Ludolph, Ingo (Frontiers in Surgery, 2022)
Background: Hidradenitis suppurativa is manifested by painful abscesses and scarring of sweat glands. Axillary, inguinal and genital regions are mostly affected. Multiple options exist in the treatment of hidradenitis suppurativa. The aim of this retrospective, mono-center cohort study was to analyze the outcome of different treatment methods after radical excision of hidradenitis suppurativa. Methods: We retrospectively evaluated the treatment strategy and recurrence rate of hidradenitis suppurativa. We included all eligible patients of legal age between February 2003 and October 2021, with the diagnosis of Hidradenitis suppurativa and the necessity for surgical treatment. All patients with surgical treatment and direct wound closure by suture were excluded. Bacterial load and flora were analyzed for primary and secondary reconstruction in combination with negative-pressure wound therapy. Patient data were analyzed for recurrence rate and remission time according to different reconstructive techniques. Results: In 44 affected anatomical sites (n = 23 patients) we treated 15 patients with negative-pressure wound therapy. Bacterial load and flora were lower in the last wound swab of patients with multi-surgical procedures (22 localizations) compared to the first wound swab independent of the use of negative-pressure wound therapy. Wound closure, independent of a direct and multi-stage procedure was achieved by local fasciocutaneous flaps (n = 12), secondary intention healing (n = 7), secondary intention healing with buried chip skin grafts (n = 10), or split-thickness skin grafts (n = 15). Radical excision combined with split-thickness skin grafts showed the lowest recurrence rate in the follow-up (16%; n = 4). Conclusion: Radical excision of hidradenitis suppurativa as gold standard for surgical treatment combined with negative-pressure wound therapy as multi-stage procedures ultimately reduced bacterial load and flora in our study. The use of split-thickness skin grafts showed the lowest recurrence rate.
CRIS-Team Scopus Importer:2022-07-22
Keywords: acne inversa; bacterial burden; flap surgery; hidradenitis suppurativa; negative-pressure wound therapy

Topical negative-pressure wound therapy: emerging devices and techniques - Horch, Raymund E.; Ludolph, Ingo; Müller-Seubert, Wibke; Zetzmann, Katharina; Hauck, Theresa; Arkudas, Andreas; Geierlehner, Alexander (Expert Review of Medical Devices, 2020)
Introduction: The treatment of chronic wounds constitutes a massive financial burden to society and our health-care system. Therefore, efficient wound care is of great importance to all kinds of medical fields. The implementation and modification of negative-pressure wound therapy can be seen as a major improvement in wound healing. Many different NPWT applications evolved trying to address various wound etiologies. Areas covered: This review aims to give an overview of various NPWT applications, show its effects on wound healing, and discuss future modifications. Expert opinion: NPWT as a delivery device for cold plasma, growth factors, or targeted stem cells to the wound bed and the ability to monitor the inflammatory activity, bacterial load and wound healing factors can be seen as possible future steps to individualized wound care. In addition, it requires high-quality experimental studies to develop the ideal foam in terms of microstructure, pore size, and material properties.
CRIS-Team WoS Importer:2020-01-31

Treatment of a chronic vesicocutaneous fistula and abdominal wall defect after resection of a soft tissue sarcoma using a bipedicled latissimus dorsi and serratus anterior free flap - Ludolph, Ingo; Apel, Hendrik; Horch, Raymund E.; Beier, Justus (International Journal of Urology, 2014)
We present a surgical treatment for bladder reconstruction in a case of chronic vesicocutaneous radiation-induced fistula and reconstruction of the abdominal wall after resection of a liposarcoma in the rectus abdominis muscle. Fistulas are sequelae after radiotherapy. To regain bladder function and reconstitute abdominal wall stability, a microsurgical flap approach should be considered. A male patient underwent resection of a liposarcoma in the rectus abdominis muscle with adjuvant radiotherapy, suffering from a chronic vesicocutaneous fistula. A bipedicled combined latissimus dorsi and serratus anterior flap was carried out after resection of the fistula for reconstruction of the urine bladder and the abdominal wall. Ascending urethrography 4 weeks postoperatively showed no leakage. In the 4-month follow-up period, no signs of recurrence of the fistula or herniation occurred. A bipedicled flap allowed reconstruction of the urine bladder and the abdominal wall. Using non-irradiated, well-perfused intra-abdominal muscle tissue over the urine bladder prevented recurrence of the fistula.
EVALuna2:15568

Vein Visualization With a Near Infrared Imaging Device and Its Impact on Students' and Nurses' Skills in an Academic Teaching University Hospital - Renno, Isabell; Horch, Raymund E.; Ludolph, Ingo; Cai, Aijia; Arkudas, Andreas (Journal of Infusion Nursing, 2024)
Venipuncture for blood collection is frequently delegated to medical or nursing students, while their individual skills depend on the quality of teaching. The aim of this study was to evaluate the use of a near infrared imaging (NIR) system on the visualization of veins and its potential benefit for the education of medical personnel. Participants answered a questionnaire following standardized venipuncture for blood sampling with the help of an NIR device. Vein visibility with the NIR device and its ability to facilitate venipuncture were examined. Visibility of veins was significantly better with the NIR, and its direction was clearly delineated. Sixty-nine percent of the participants stated that they felt more secure with venipuncture after using the NIR device. Patients' individual factors limited the visibility of veins. The adjuvant use of an NIR system for venipuncture improves participants' subjective skills through visualization of veins and their direction.
CRIS-Team Scopus Importer:2024-07-19

Wound closure by means of free flap and arteriovenous loop: Development of flap autonomy in the long-term follow-up - Rother, Ulrich; Müller-Mohnssen, Helena; Lang, Werner; Ludolph, Ingo; Arkudas, Andreas; Horch, Raymund E.; Regus, Susanne; Meyer, Alexander (International Wound Journal, 2019)
Free flaps in combination with arterial reconstruction by means of arteriovenous loops or bypass have, meanwhile, been established as a therapeutic option in defect reconstruction for areas without recipient vessels. Our aim was to analyse the long-term performance, flap autonomy, and the flap perfusion. Patients receiving this combined reconstruction at a single-centre institution were included. During follow-up examination, the patency of arterial reconstruction was investigated by duplex ultrasound. Flap micro-circulation was assessed by laser Doppler flowmetry and white light tissue spectrometry (O2C) as well as by indocyanine green fluorescence angiography. Twenty-three patients could be clinically followed up. Duplex ultrasound showed, in four cases, arterial pedicle occlusion in spite of vital flap. Comparison of the O2C perfusion parameters between flaps with occluded pedicles and those with intact inflow showed no significant difference (parameters sO2: P =.82; Flow: P =.31). Similar results were obtained by fluorescence angiography; no significant difference could be detected between both groups (parameters Ingress P =.13; Ingressrate P =.54). Combined vascular reconstruction with free tissue transfer is associated with a good long-term outcome and wound closure. Even after flap transplantation to areas with critical tissue perfusion, the flap can develop autonomy and thus survive after pedicle occlusion.
CRIS-Team Scopus Importer:2019-11-19
Keywords: arteriovenous loop; flap autonomy; flap perfusion; indocyanine green; laser Doppler